Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Cuproptosis in hepatocellular carcinoma: bridging copper homeostasis with therapeutic horizons - Songsong Fan; Aoqing Wang; Rui Peng; Jun Cao; Daoyuan Tu; Bingbing Su; Jiahao Zhang; Shengjie Jin; Guoqing Jiang; Chi Zhang; Dou-Sheng Bai (Molecular Biology Reports, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Continuous versus discontinuous biodegradable film mulching in maize: A five-year field study on soil carbon sequestration, productivity, and microplastic legacy - Kai Wang; Xiao Li; Shiyan Sun; Gary Y. Gan; Ying Zhao; Qiang Li; Jiangxin Gu; Rui Jiang (Field Crops Research, 2026)

NIR-responsive mesoporous core-shell nanoplatform with oxygen self-supply and cascade targeting for reversing doxorubicin resistance via synergistic chemo-phototherapy - Yufeng Li; Yuping Jiang; Kexuan Wang; Xinyi Liu; Rui Yang; Lu Han; Tao He; Na Li; Da Huo (Chemical Engineering Journal, 2026)

Machine learning-guided discovery of poly(ethylene terephthalate)-binding modules to enhance durable whole-cell degradation - Rui Long; Yaxin Tang; Chengyong Wang; Tangli Yang; Wei Liu; Ling Jiang (Bioresource Technology, 2026)

Overview of research on fire smoke diffusion and control in tunnels with different connection structures - Yongzheng Yao; Yiyuan Wang; Rui Wang; Luyao Tan; Tao Du; Lei Jiang; Kun He; Zihe Gao; Zeng Long (Tunnelling and Underground Space Technology, 2026)

Nonradical pathway in peroxymonosulfate-based Fenton-like reactions triggered by the active Fe-Cu dual sites encapsulated in endogenous N-rich biochar - Rui Yang; Chaoting Jiang; Wangbo Wang; Xianshu Zhou; Fangshu Xie; Mingming Ta; Tuo Wang; Haifang Cai; Juan Guo; Weihuang Zhu (Journal of Environmental Chemical Engineering, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Utilization of spent biochar as a novel adsorbent and catalyst for the removal of ciprofloxacin from water: Insights into the performance and mechanisms - Xiaohong Hu; Tao Jiang; Bing Wang; Rui Li (Journal of Environmental Chemical Engineering, 2026)

Co-inoculation of lactic acid bacteria improves silage quality and mitigates antibiotic resistance gene transmission by restructuring the microbial community in hybrid Pennisetum silage - Duoting Wu; Wan Zhong; Zhisheng Wang; Xinyan Tao; Liyuan Shi; Peng Dai; Fali Wu; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Yiping Tang; Huawei Zou; et al. (Journal of Environmental Chemical Engineering, 2026)

Identification and functional characterization of interferon c (IFNc) in orange-spotted grouper (Epinephelus coioides) involved in antiviral response to SGIV and RGNNV infections - Yanjie Shi; Rui Jiang; Xiaotian Zhuo; Jiaji Chen; Zhiwen Wang; Yishan Lu; Zhen Gan (Fish & Shellfish Immunology, 2026)

Machine learning models reveal the spatial distribution and key environmental drivers of Coilia nasus in East China Sea's coastal waters - Zeyu Xiao; Jiarong Shen; Haoran Wang; Rijin Jiang; Jianxiong Li; Rui Yin; Jiaying Zeng; Mingyuan Cui (Estuarine, Coastal and Shelf Science, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Enhanced degradation of sulfamethoxazole in dielectric barrier discharge plasma via Zn tetrahedral site doping-mediated d-band center engineering of CoFe2O4 - Xiaojing Wang; Rui Cao; Na Huang; Mengmeng Du; Mingyao Yuan; Jia Ma; Fan Zhang; Jiaqi Jiang; Zhenxing Zeng; Yanzong Zhang; Zhilin Li; Shihuai Deng (Chemical Engineering Journal, 2026)

Synergistic Effect of Indole-3-Acetic Acid and Homogeneously Dispersed Ulva prolifera-Derived Carbon Quantum Dots in Enhancing CO2 Fixation, Biomass Production, and Macromolecules in Chlorella vulgaris - Chuande Liu; Hao Chen; Yuye Jiang; Rui Zhang; Linzhu Peng; Shuang Wang; Esakkimuthu Sivakumar (Bioresource Technology, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Harnessing a MMP-sensitive fluorescent probe for in-situ and reversible monitoring MMP alteration in dual color based on aggregation/monomer mechanism - Mengmeng Wei; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Yi Qian; Jing Xu; Xiaoyan Tang; Jiaojiao Liu; Shenqiang Wang; Tingwang Jiang; Xifeng Yang; Xuekun Hong; et al. (Analytica Chimica Acta, 2026)

Seed Germination in Red Mud: Roles of Plant Traits and Metal Availability - Jian-Rui Wang; Jian-Xiong Liao; Qian-Wen Jiang; Ling Mo; Rui-Xia Ma; Jing-Jing Feng (Water, Air, & Soil Pollution, 2026)

Load transfer mechanism of O-cell method for offshore foundation considering nonlinear pile-soil interface response - Rui Jiang; Yuke Wang; Zhengyu Fan; Junjing Zhang; Meiju Jiao (Marine Georesources & Geotechnology, 2026)

Paleoenvironmental response in the South China Sea from the Middle Miocene Climatic Optimum to Middle Miocene Climate Transition: Geochemical records from an isolated carbonate platform - Ning Guo; Wei Jiang; Tianlai Fan; Shendong Xu; Rui Wang; Jian-xin Zhao; Yue-xing Feng; Kefu Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Divergent effects of biodegradable and conventional microplastics on denitrification in soils: Mechanisms governing N₂O emission and product stoichiometry - Hao Zhang; Xiao Li; Minhang Zhu; Rui Wang; Jinbo Zhang; Christoph Müller; Rui Jiang (Journal of Hazardous Materials, 2026)

Adaptive genetic trade-offs govern the enantioselective degradation and horizontal transfer of ibuprofen catabolic genes - Weihao Zhu; Mingli Jiang; Rui Fan; Kaihua Pan; Shenghao Wang; Lu Huang; Qiantong Ru; Yinhu Jiang; Qian Li; Qian Zhu; Mingliang Zhang; Zhijian Ke; et al. (Journal of Hazardous Materials, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

How phosphorus enrichment regulates the microbial community resistance and multifunctions tolerance to drying–rewetting cycles in paddy fields: the critical role of stoichiometry - Jiaying Wang; Yi Xu; Tinghong Fu; Guoxiang You; Rui Wang; Tianyun Li; Zewei Jiang; Shihong Yang (Journal of Environmental Management, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Two-phase flow in clayey silt hydrate reservoirs drives migration and clogging of fine clay particles - Jiang Lei; Wei Guo; Yuan Wang; Wen Zhang; Huie Chen; Pengyu Zhang; Rui Jia (Engineering Geology, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Carbon radical-promoted NH bond breaking for biomass-derived amino acids to nitriles on low-coordinated Ni centers - Huiwen Zhang; Xia Zhang; Yue Ma; Yingnan Zhao; Rui-Qi Yao; Xinying Sun; Tonghui Wang; Beibei Xiao; Gao-Feng Han; Xing-You Lang; Qing Jiang (Chemical Engineering Journal, 2026)

Kinetic-driven separation of ethylene from ternary mixtures by engineering the crystal size of a novel 2D metal-organic framework - Wenlei Yang; Lingyao Wang; Guangzu Xiong; Yunjia Jiang; Dong Fan; Rui-Biao Lin; Guillaume Maurin; Yuanbin Zhang; Banglin Chen (Chemical Engineering Journal, 2026)

Folic acid alleviates heat stress-induced ovarian dysfunction in dairy cows via modulation of follicular fluid metabolism and ABC transporter activity - Yaochang Wei; Yifan Yang; Yifan Li; Zhuangsheng Wang; Tingting Deng; Xiaojiao Hu; Xuefeng Jiang; Rui Xiao; Yanfang Wu; Suzhu Qing; Yongsheng Wang (Animal Reproduction Science, 2026)

Correction to: Antibacterial activity and mechanism of rutin in UV-A light treatment against Escherichia coli O157:H7 - Jiahui Wang; Yuzhang Zhu; Tao Liu; Xiangyu Hong; Mi Liu; Rui Zhou; Xianke Li; Mingguo Jiang; Lifang Yang (Archives of Microbiology, 2026)

Equine piroplasmosis in China, 2000 to 2025: a systematic review and meta-analysis of prevalence and risk factors - Di Jiao; Wei Wei; Xinyue Dong; Rui Shi; Rigai Sa; Chengyu Ma; Pengcheng Bian; Ke Liu; Lianlong Wang; Ziyao Wei; Hanyi Jiang; Rui Wang (The Veterinary Journal, 2026)

On-chip squeezed light in the audio frequency band - Xuezhi Zhu; Yunyun Cao; Rui Liu; Yaya He; Fan Zhang; Yaqing Zhang; Shiwei Du; Meihong Wang; Xiaoshun Jiang; Xiaolong Su (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Asymmetric diamide resistance conferred by ryanodine receptor G4946E/V mutations in Plutella xylostella - Xingliang Wang; Dong Jiang; Rui Hu; Shuwen Wu; Yu Shi; Yihua Yang; Yidong Wu (Pesticide Biochemistry and Physiology, 2026)

Numerical study of the flow field effect of turbulent reef units under different deployment configurations - Jiayi Wang; Rui Pan; Zhu Li; Xiaoran Liu; Qiwen Liang; Zhaoyang Jiang (Ocean Engineering, 2026)

Groundwater-mediated controls and future projections of carbon stocks in coastal wetlands - Xulong Gong; Ying Liang; Xue Jiang; Rui Ma; Yuan Liu; Shun Hu; Yanxin Wang (Journal of Hydrology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Mitigating bioaerosol exposure risks in high-traffic clinics: Experimental and numerical optimization of air purifier interventions - Yongxin Wang; Zhijian Liu; Lei Jiang; Zirun Shi; Zijian Li; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2026)

Initial exploration of the health effects on Qinghai-Tibetan Plateau yaks following short-term exposure to polystyrene microplastics: Analysis of rumen microbiota, host metabolism, antioxidant function and inflammatory responses - Penghu Zhang; Yanbing Zhu; Zhisheng Wang; Peiqiang Yu; Bai Xue; Lizhi Wang; Rui Hu; Huawei Zou; Yahui Jiang; Jianxing Xiao; Cui Tan; Fali Wu; et al. (Journal of Hazardous Materials, 2026)

Enhancement of microbial protein production via hydrogen oxidizing bacteria in microbial electrolytic protein-production cell system - Rui Dong; Hangyu Sun; Yilin Jiang; Haotian Liu; Yue Wang; Xingjia Fu; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2026)

Magnetite-phase steel slag-peroxymonosulfate promoted volatile fatty acids recovery from anaerobic fermentation of food waste: Substrates structure disruption and metabolic regulation - Xiupeng Jiang; Wei Wang; Youcai Zhao; Wenxiao Zhang; Xi Li; Rui Zhang; Xiaoya Li; Tao Zhou (Journal of Environmental Chemical Engineering, 2026)

Optimization of magnetic field-assisted freezing via response surface methodology and its impact on blueberry freeze-thaw quality - Bowen Chen; Xinqun Zhou; Jing Sun; Rui Wang; Min Zhang; Ning Ji; Tingchao Liu; Bangdi Liu; Lihua Jiang (International Journal of Refrigeration, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Development of a triplex RT-qPCR assay for rapid and accurate detection of porcine rotavirus, porcine epidemic diarrhea virus, and porcine deltacoronavirus - Yuhan Yang; Xingyu Xiao; Meixuan Ren; Ningning Jiang; Xiaoxu Xie; Xue Zheng; Rui Yin; Shiyu Luan; Jingnan Wang; Peng Li (Veterinary Research Communications, 2026)

Microbial inoculation in green roofs: progress, challenges and ecological regulation strategies - Nan Yang; Hechen Li; Yihan Wang; Pingrui Jiang; Shaobo Gao; Hongyuan Li; Rui Hua; Xinjian Shi; Guang Hao (Urban Ecosystems, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

MECP2T203M mutation disrupts neurogenesis in human cerebral organoids by altering chromatin dynamics and transcriptional regulation - Zhihong Song; Qian Zhu; Rui Yang; Huihui Jiang; Ying Li; Liping Chen; Ting Wang; Yan Wu; Yan Liu; Haitao Wu (Science China Life Sciences, 2026)

Antibacterial activity and mechanism of rutin in UV‑A light treatment against Escherichia coli O157:H7 - Jiahui Wang; Yuzhang Zhu; Tao Liu; Xiangyu Hong; Mi Liu; Rui Zhou; Xianke Li; Mingguo Jiang; Lifang Yang (Archives of Microbiology, 2026)

CRISPR/Cas9 system inhibits largemouth bass virus infection in vitro and in vivo - Rui-Long He; Mao-sheng He; Xin-Yuan Jiang; Yi-Wang; Hao-Liang; Xiang-Yi Bu; Kun Xu; Fei Ling; Gao-Xue Wang; Hai-Feng Jiang (Aquaculture, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

Lithium Enhances Survival Bias Associated with the Lateral Habenula Suppression - Kunlin Liu; Rui Zhu; Haoyue Guo; Jinghuan Li; Qianfu Wang; Yi He; Chenggang Zhu; Zheng Ma; Xiaodan Jiang; Jack van Honk; Jin Bao (Neuroscience Bulletin, 2026)

From copper imbalance to immunometabolic remodeling: cuproptosis-related vulnerability and therapeutic hypotheses in autoimmune diseases - Yang Shao; Rui feng Zhang; Zhonghe Wang; Jiali Gan; Xi juan Jiang; Lin Yang; Zhi jie Song (Inflammation Research, 2026)

An experimental study on water migration near clay–caisson interface under long-term cyclic loading - Lijun Ke; Rui Tan; Yaotian Gu; Shengwei Wang; Jiang Xu; Yufeng Gao (Marine Georesources & Geotechnology, 2026)

Experimental investigation on anisotropic behavior of Yellow River silt with different initial water contents and confining pressures - Yuke Wang; Jie Wu; Shuaiqiang Bai; Changnv Zeng; Rui Jiang (Marine Georesources & Geotechnology, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Micro-nano biochar interfaces promote adsorption-reduction coupling to accelerate bioelectrodechlorination in groundwater - Zena Zhang; Miao Lv; Rui Wang; Bo Wang; Ruoyu Du; Yuxuan Lou; Chunlin Wang; Xiaodun Jiang; Hai Hou; Zhiling Li; Fan Chen (Journal of Hazardous Materials, 2026)

CO2-temperature-water nexus reshaping cherry tomato flavor: Multimodal sensing with E-nose and GC-IMS - Rui Li; Xinru Ren; Yilin Wang; Mengyan Jiang; Rongqun Wang; Zhi Zhang (Food Chemistry, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Generation and characterization of the monoclonal antibody against the heavy chain of American eel (Anguilla rostrata) IgM - Xiaolong Meng; Shuangshuang Cao; Hongjun Xie; Wenting Jiang; Rui Guo; Yuchen Zhuo; Qicheng Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2026)

Multi-level design of a chitosan-based membrane: from sisal fiber reinforcement to surface micropatterning and hybrid hap for enhanced bone regeneration - Shuo Tang; Rui Lin; Yuqing Wang; Xinyuan Feng; Fang Shi; Yupeng Guo; Shu Huang; Xiang Hu; Liuyun Jiang (Carbohydrate Polymers, 2026)

Evaluation of the aerosol transmission patterns and the airflow organization effectiveness in the respiratory outpatient clinic - Yongxin Wang; Lei Jiang; Zhijian Liu; Duo Cai; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Building and Environment, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Short-term organic fertilizer substitution: effects on crop yield and soil phosphorus dynamics in a rice-rapeseed rotation system - Hui Wang; Wenlong Cheng; Shang Han; Shan Tang; Fahui Jiang; Rongyan Bu; Min Li; Rui Zhu; Mengmeng Tang; Zhenghua Xu; Ji Wu (Journal of Soils and Sediments, 2026)

A multi-strategy integrated heuristic algorithm for the container relocation problem in automated container terminal yards - Yipeng Jiang; Yong Zhang; Lei Zhang; Zhen Li; Chengji Liang; Rui Zhao; Yu Wang; Panlong Wang (Frontiers in Marine Science, 2026)
As the operational scale of automated container terminals continues to expand, the impact of the container relocation problem on operational efficiency and cost has be-come increasingly significant. To address the issues of excessive relocations and low operational efficiency during container retrieval within a bay, a container relocation optimization model for the yard is developed. On this basis, a bay-oriented heuristic algorithm is proposed by incorporating practical operational rules and operational experience. The algorithm prioritizes empty stacks, non-blocking stacks, and stacks with the minimum number of blocking containers. It further integrates the nearest-placement rule and safety height constraints to achieve efficient and rational relocation decisions for blocking containers. Numerical experiments with different problem scales are conducted to validate the effectiveness of the proposed method. The results show that, in small-scale instances, the proposed algorithm effectively reduces the number of relocations. In large-scale instances, its advantage becomes more pronounced as the problem size increases. Compared with the traditional nearest-placement rule, the proposed algorithm consistently achieves superior performance across different scales: the number of relocations is reduced by up to 15, the relocation rate decreases by an average of 56%, and the operational cost is reduced by approximately 35.85% on average.

Dihydromyricetin attenuates LPS-induced liver injury in chicks through the JNK signaling pathway - Lina Jia; Jiarui Liu; Zhenghua Ji; Liang Yuan; Yingchao Gong; Xinru Jiang; Xianan Fan; Changwen Li; Rui Li; Haoran Wang; Fangping Liu (Research in Veterinary Science, 2026)

Microplastics enrich and disseminate antibiotic resistance genes in seawater: Enhanced effects of aging and biodegradability of microplastics - Jianhong Shi; Chengyuan Ji; Chaoli Sun; Changhai Jiang; Baoyi Lv; Rui Wang (Journal of Environmental Chemical Engineering, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

One-step hydrothermal synthesis of Sm-doped BiOIO3 for enhanced photocatalytic removal of mercury from flue gas - Yixuan Shen; Zijian Xiang; Jiang Wu; Sheng Wang; rui Zhu; Yaji Huang; Shaohua Liang; Jingxin Xu; Xueli Sun; Xiuyong Zhao (Fuel, 2026)

Development of antibacterial and antifouling smart/active food packaging based on phosphorylcholine-modified chitosan for pork freshness monitoring and raspberry preservation - Tiantian Liu; Jiayi Xue; Ruoran Qin; Haoqiang Wang; Rui Zhang; Yingzhu Liu; Longwei Jiang (Food Packaging and Shelf Life, 2026)

Drivers of reduction in PM2.5 concentrations and related health risks in China from 2013 to 2023 - Fenfen Zhang; Rui Liu; Mei Wan; Yanning Zhang; Yueqi Jiang; Zhaoxin Dong; Qian Song; Lyuyin Huang; Qingru Wu; Litao Wang; Jiayu Xu; Shuxiao Wang (Environmental Pollution, 2026)

Mimicking leaves hierarchical differential pore architecture integrated with electric/magnetic inverse gradient structure for green EMI shielding and thermal infrared stealth - Dingwen Yin; Jinbao Li; Rui Cheng; Huijuan Xiu; Gengmei Liu; Feiguo Hua; Xuanchen Jiang; Yuxin Qin; Xia Wang (Chemical Engineering Journal, 2026)

Coordinatively robust and toughen plant protein adhesives via the synergy of oligomer domain cross-linking and hierarchical dissipation architecture - Wujie Huang; Zhenghui Lei; Ao zhang; Rui Xu; Jiawei Shao; Xianwei Wang; Shuaicheng Jiang; Jianzhang Li; Xiaona Li (Chemical Engineering Journal, 2026)

Interface-engineered MXene/OCNT fibers for high-performance wearable supercapacitors - Rui Wang; Xupu Jiang; Ting Ding; Wujun Ma; Chuntao Lan; Min Li (Chemical Engineering Journal, 2026)

Excavation Damage Evaluation of Rock Anchor Beam Based on Acoustic P-Wave Velocity and RFD Index in Highly Stressed Powerhouse: A Case Study of Baihetan Hydropower Station, China - Jin-Shuai Zhao; Lei Xia; Yong Fan; Quan Jiang; Bing-Rui Chen; Guang-Dong Yang; Dong-Ze Wang (Rock Mechanics and Rock Engineering, 2026)

The Impact of Climate Change on the Potential Habitat Distribution of Eggs and Larvae of the Liza haematocheilus and Harpadon nehereus in the Coastal Waters of Zhejiang Province - Yuelian He; Rijin Jiang; Rui Yin; Peng Zhao; Mengyuan Zhang; Jinqing Wang (Journal of Marine Science and Engineering, 2026)
In recent years, climate change has increasingly shaped the potential habitat distribution of marine fishes, rendering this topic a focal area in marine ecology and biogeographical research. Using the MaxEnt modeling approach, this study projects the current and future potential habitats of eggs and larvae of two ecologically and economically important coastal species, the Liza haematocheilus and the Harpadon nehereus, across the nearshore waters of Zhejiang Province. Distribution records of early life stages and key environmental variables were integrated to model suitability under present-day conditions and three Shared Socioeconomic Pathway–Representative Concentration Pathway climate scenarios: SSP2-4.5, SSP3-7.0, and SSP5-8.5. Results identify sea surface salinity, surface current velocity, and sea surface temperature as the primary drivers of habitat suitability for Liza haematocheilus early-life stages; in contrast, chlorophyll-a concentration emerges as an additional significant predictor for Harpadon nehereus, alongside the aforementioned three variables. Under contemporary climatic conditions, high-suitability habitats for Liza haematocheilus eggs and larvae are predominantly concentrated in estuarine and island-adjacent nearshore zones, constituting 40.76% of the total predicted suitable area. For Harpadon nehereus, high-suitability areas are broadly distributed across nearshore shelf waters, representing 65.57% of its total modeled suitable habitat. Projected under future scenarios, the largest absolute increase in high-suitability area for Liza haematocheilus occurs under SSP3-7.0 in the 2050s (+0.38 × 104 km2), whereas Harpadon nehereus exhibits its greatest expansion under SSP5-8.5 in the 2090s (+0.45 × 104 km2). Collectively, the total suitable habitat area for Liza haematocheilus is projected to expand across all three scenarios, while that of Harpadon nehereus remains relatively stable overall—yet its high-suitability fraction increases markedly under high-emission, high-warming conditions. These findings suggest that ongoing climate warming may facilitate range expansion and enhanced nursery habitat availability for both species in Zhejiang’s coastal zone, positioning them as potential ecological beneficiaries of regional climate change.

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Mobilization of cadmium and lead mediated by iron and manganese reduction in coastal wetlands of Yueqing Bay, China - Qing-Rui Jiang; Jia-Xi Pang; Wei-Wei Ma; Wen-Zhuo Zhu; Jian Wang; Xiao-Ping Chai; Lu-Ping Song; Yi-Ying Zhang; Jian-Xin Wang (Marine Pollution Bulletin, 2026)

Dynamic recovery sequence optimization of subway-bus network with constrained reinforcement learning - Shan Liu; Zhenhao Meng; Rui Jiang; Zhengli Wang; Ya Zhang; Ying-En Ge (Transportation Research Part D: Transport and Environment, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A machine learning approach coupling immediate and lagged drivers to predict sand and dust storms in Northern China - Mile Wang; Kunxia Yu; Peng Li; Zhanbin Li; Rui Yan; Zixia Jiang; Xue Li; Lu Jia (Journal of Environmental Management, 2026)

Ultra-low temperature adsorption of propane to achieve layered Ni3V2O8/NiO synergistic catalysed oxidative dehydrogenation of propane to propylene - Rui Liao; Yun Yang; Peiting Jiang; Fengyu Ji; Yuhang Qian; Lulu Li; Xuyu Wang; Xinwei Zhou; Hongbing Ji (Fuel, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Biomass-derived modifiers customize polymeric nanofiltration membranes for enhanced lithium/magnesium ion selectivity - Xin-Xi Ding; Cheng Jiang; Jia-Wang Wang; Zi-Hui Wu; Rui Luo; Yue Zhao; Yue Wang; Dan-Dan Shao (Desalination, 2026)

Biotransport and biotransformation of arsenic in earthworm tissues: Advancing vermiremediation strategies of soil contamination - Yunxiang Xu; Muyuan Wang; Yizhao Wu; Yifan Zhang; Rui Jiang; Qi Zhao; Jibao Jiang; Hao Qiu; Yinsheng Li (Chemical Engineering Journal, 2026)

Cortical Contributions to Local and Global Biological Motion Perception: Insights from Transcranial Magnetic Stimulation - Lianzi Xing; Zhongju Sun; Yushu Wang; Yiru Bao; Peng Cai; Rui Wang; Yi Jiang (Neuroscience Bulletin, 2026)

A Novel Elastoplastic Dynamic Damage Constitutive Model and Numerical Implementation of Rock Under True Triaxial Multistage Disturbance - Zhi Zheng; Yihuai Zhang; Guoxiong Mei; Haibo Jiang; Wei Wang; Rui Pan; Shaojun Li (Rock Mechanics and Rock Engineering, 2026)

Effects of bacteria-microalgae immobilization on physiology, immunity, microbial composition, and vibriosis resistance of sea cucumber (Apostichopus japonicus) - Xuda Wang; Zunchun Zhou; Ying Dong; Rui Mi; Jingwei Jiang; Danni Liu; Bo Ye; Xiaoyue Wang; Zhenjun Zhao; Boxue Yang; Shilei Li (Aquaculture, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Geochemical transformation of ferrihydrite: A review on mechanisms, effects of coexisting molecules and environmental implications - Yupeng YAN; Cheng WANG; Muammar MANSOR; Rui JIANG; Xiaoming WANG; Qin ZHANG; Xionghan FENG; Wenfeng TAN; Andreas KAPPLER; Biao WAN (Pedosphere, 2026)

Recent progress and strategic perspectives of Na3V2(PO4)2F3 cathode: mechanisms, syntheses, and modifications in zinc-ion batteries - Rui Jiang; Jiajie Zhou; Sheng Ouyang; Xiaoyan Shi; Junling Xu; Xiang Wang; Lianyi Shao; Zhipeng Sun (Next Research, 2026)

Unveiling the mechanistic in polarized light excited dissolved organic matter degrading contaminant: Energy transfer or electron transfer - Gang Wang; Pengcheng Huang; Qiyuan Sun; Feifeng Wang; Jiejie Chen; Yayin Jiang; Yuyi Zheng; Rui Ding; Tianfang Zhang; Bin Zheng; Zhiqiang Zhang (Journal of Environmental Chemical Engineering, 2026)

Bimetallic sulfide catalysts photocatalytically reduce carbon dioxide into high-value fuels: A review - Chenyue Hua; Kai Xie; Cheng Peng; Jiang Wu; Sheng Wang; Jingxin Xu; Kai Huang; Xueli Sun; Hai Zhang; Rui Zhu; Ping He; Ahmad Hosseini-Bandegharaei (Journal of Environmental Chemical Engineering, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Secondary salinization in facility agricultural soils detrimentally affects the spatial distribution of earthworm communities: dominant drivers and ecological risks - Yifan Zhang; Yizhao Wu; Muyuan Wang; Rui Jiang; Yunxiang Xu; Qi Zhao; Jibao Jiang; Ke Song; Weiguang Lv; Yinsheng Li (Journal of Environmental Management, 2026)

Development of a pectin-based edible active packaging film incorporating curcumin-loaded multilayer nanoparticles to extend the shelf-life of blueberry - Ruoran Qin; Yanyan Wang; Jiayi Xue; Tiantian Liu; Rui Zhang; Haoqiang Wang; Longwei Jiang (Food Hydrocolloids, 2026)

Integrated plastic film and straw mulching enhances potato tuber yield in mountainous regions by optimizing rhizospheric metabolites and root–microbe interactions - Kang Du; Xinyue Yang; Zhenpeng Deng; Xi Lin; Mengyuan Hu; Rui Jiang; Guolian Zheng; Xiaoping Yi; Xun Liu; Changwen Lyu; Jichun Wang (Field Crops Research, 2026)

Pseudo-static test and numerical study of beam-column joints with novel replaceable energy-dissipating shear disc - Kaihang Zhang; Xiang Zhu; Rui Wang; Qing Jiang; Guangze Lei (Engineering Structures, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Functionalizing 3D DNA crystals by replacing non-framework strands - Xinyu Feng; Li Xu; Yunhan Zhang; Shuheng Wei; Dongbao Yao; Huichao Chen; Yueye Wang; Yujing Wu; Hui Hou; Xiao Cui; Qian Meng; Yue Gu; et al. (Chemical Engineering Journal, 2026)

Long-term reclamation enhances soil organic carbon accumulation via mitigating salinity and alkalinity in coastal saline soils - Wei Zhu; Shiguo Gu; Xin Zhang; Xuan Yu; Shuanghuang Yu; Xiangping Wang; Rui Jiang; Xiangtian Meng; Rongjiang Yao (Agriculture, Ecosystems & Environment, 2026)

Integrative Analysis the Role of ENG as a Metabolic and Macrophage-Related Gene in Hepatocellular Carcinoma - Songsong Fan; Yuhong Tang; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Weidi Yu; Chen Chen; Shunyi Wang; Shengjie Jin; Guoqing Jiang; Chi Zhang; et al. (Biochemical Genetics, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Revealing the key role of Pt and Pd sites in the promotion or inhibition of H2O on CO catalytic oxidation - Ning Hou; Cangpeng Shan; Xiaohua Zhu; Hui Wang; Wenbo Zhang; Qinwei Jia; Yufan Jiang; Rui Han; Qingling Liu (Fuel, 2026)

Alpaca nanobody-based sandwich ELISA for specific detection of Salmonella enteritidis in chicken - Liang Yuan; Shibo Wang; Yani Ren; Zhenghua Ji; Xinru Jiang; Beili Hao; Shuangshuang Hao; Xiaoxi Han; Changwen Li; Yicong Chang; Rui Li; Fangping Liu (Food Control, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Bioengineered functional scaffolds co-loaded with osteonectin and HA-internalizing osteoblasts for boosting bone regeneration - Wei Yang; Qin Zou; Chenxin Wang; Yuankun Ren; Rui Zhang; Mingyue Lin; Xueqi Zhang; Yu Liu; Boyang Wang; Wei Li; Li Jiang; Xiyu Li (Chemical Engineering Journal, 2026)

Damages of aged-PVC microplastics exceed the enhanced resistance of chlorella pyrenoidosa induced by phosphorus limitation - Xiao Tan; Lv Wang; Chao Xing; Zhipeng Duan; Jia Liang; Rui Zhu; Jiang Huang; Shichao Chen; Yijia Wei (Aquatic Toxicology, 2026)

How biodegradable mulching alters soil nitrogen transformations to enhance soil nitrogen supply and influence gas emissions in a maize cropping system - Hao Zhang; Kai Wang; Jinbo Zhang; Christoph Müller; Dianyuan Ding; Qiang Li; Hengliang Tang; Rui Jiang (Plant and Soil, 2026)

Glaucine suppresses IL-16/CD4 to alleviate neuropathic pain via spinal p56lck-NMDA receptor signaling - Xue Li; Rui Wang; Xiaonan Ma; Jin Yang; Shen Zhang; Zimeng Zhang; Han Jiang; Jihua Liu; Boyang Yu; Wenling Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The microbial mechanism of the impact of grazing degradation on the soil multifunctionality of the hummock wetland on the riverscape - Xiaoai Cao; Huamin Liu; Rui Zhang; Yunhao Wen; Shan Jiang; Zhichao Xu; Lu Wen; Yi Zhuo; Dongwei Liu; Ke Yu; Lixin Wang (Applied Soil Ecology, 2026)

Green and low carbon use efficiency of urban land in spatial network: structure characteristics, community division, and influencing factors - Lina Peng; Rui Ding; Juan Liang; Kexin Wang; Wenqian Xiao; Shuyue Jiang (Environment, Development and Sustainability, 2026)

Is China's energy transition pace driven by the supply-side or the demand-side? - Hu Wang; Feng Wang; Juan Liu; Rui Ling; Hao Zhang; Hongfei Jiang (Utilities Policy, 2026)

Anthropogenic heat amplification in industrial zones: Unraveling heat stress risk heterogeneity in river-sea dual-core cities - Yujie Li; Jingfu Cao; Mingcai Li; Song Jiang; Jie Yang; Rui Xin; Ping Qu; Jing Chen; Jing Wang (Sustainable Cities and Society, 2026)

Plant protoberberine alkaloids: structural diversity, biosynthesis, synthesis, biological activity, structure-activity relationships and clinical applications of berberine - Weiqi Jiang; Wen Zhang; Chenxin Jing; Han Zhou; Zhi-Jun Zhang; Rui Wang; Ying-Qian Liu (Phytochemistry, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Controls of surface water-groundwater interaction on the migration and transformation of dissolved organic matter in coastal area - Ying Liang; Xulong Gong; Rui Ma; Changjian Zou; Xue Jiang; Chen Liu; Kaige Ma; Yuan Liu; Yanxin Wang (Journal of Hydrology, 2026)

Determining the source contributions of dissolved organophosphorus compounds in lake water utilizing FT-ICR-MS and PCA-APCS-MLR receptor models - Xinrui Jiang; Yao Du; Mengze Li; Rui Xu; Tianming Wu; Baisong Deng; Dandan Si; Wen Zhang; Jingwen Yu; Yanxin Wang (Journal of Hydrology, 2026)

Analysis of kinematic characteristics of geohazards along the Karakoram Highway using multi-track time series InSAR observations - Bei An; Changcheng Wang; Yanan Jiang; Peng Shen; Chen Liu; Kui Liu; Rui Wang (Geomorphology, 2026)

Insights into the effects of different nitrogen sources on microbial metabolic function and biodegradation of bituminous coal - Yundu Yang; Bingjun Liu; Sheng Xue; Junyu Wang; Xiangqing Jiang; Ruifeng Chen; Rui Sun; Keyang Cheng (Fuel, 2026)

Performance analysis of an ammonia-kerosene dual-fuel novel SOFC-turboprop engine aviation hybrid system with chemical heat recovery - Xinyan Xiu; Rui Wang; Cong Wang; Jiwei Fang; Meng Zhao; Chenghao Li; Sibo Wang; Jiang Qin; Hongyan Huang (Fuel, 2026)

Efficient elimination of highly lethal Vibrio parahaemolyticus in shrimp aquaculture by a vibriophage - Mingrui Li; Huaijin Jiang; Keming Shi; Haoyu Huang; Xiaojun Wang; Fang Li; Ke Pan; Yunlan Yang; Rui Zhang (Fish & Shellfish Immunology, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

A new isoflavone from processed root barks of Paeonia suffruticosa and their procoagulant activity - Shuo-Guo Li; Rui Yang; Mi-Mi Lu; Shu-Mei Wang; Jiang Meng (Natural Product Research, 2026)

Climatological characterisation and trends of extreme winds and their application to power transmission lines in China - Hongyu Wang; Cong Jiang; Feifei Mu; Kai Liu; Rui Mao; Xin Yin (Natural Hazards, 2026)

Stronger Adaptability of Eukaryotic Communities than Prokaryotes in Seawater across an Extensive Salinity Gradient - Shan Gao; Wei Zhao; Xiaoyan Guan; Zelong Zhao; Bai Wang; Yao Xiao; Guohan Zhang; Yongjia Pan; Hongjuan Sun; Pingzhe Jiang; Rui Mi; Jingwei Jiang; et al. (Marine Biotechnology, 2026)

Spatiotemporal modeling of oxygen transport and layered regulation in tidal flow constructed wetlands - Rui Ma; Lanlan Fu; Jiangsen Ma; Lei Jiang; Yiyuan Zhuo; Linsong Cheng; Fangying Ji; Xiaoming Wang (Water Research, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Assessing pollutant leaching and migration from underground coal gasification residual coke - Yi Cheng; Caifang Wu; Rui Yang; Fangfang Wang; Xiuming Jiang; Shuai Xu (Process Safety and Environmental Protection, 2026)

Role of PFAS in gas–liquid displacement in unsaturated porous media: a pore-scale study - Mingxiu Zhan; Ninghua Zhan; Jingchi Zhang; Hongjie Jiang; Wentao Jiao; Jinqing Wang; Yongping Shan; Xu Xu; Abdolreza Kharaghani; Evangelos Tsotsas; Rui Wu (Journal of Hydrology, 2026)

Cropping systems reshape the distribution and risks of microplastics in soil aggregates in a karst agricultural region - Feng Jiang; Rui Wu; Yuman Ma; Yanxia Wang; Qibo Chen; Qibin Liang; Lei Hou (Journal of Hazardous Materials, 2026)

Migration and transformation mechanism and ecotoxicity of heavy metals in shale gas exploitation: Research progress and challenges - Hualin Zhang; Xiaoliang Jiang; Rui Wang; Tinggang Li (Journal of Hazardous Materials, 2026)

Developing a radio frequency disinfestation technology for red jujubes with BaTiO3 as a filling material: Pest mortality, energy efficiency, and product quality - Xin Ye; Junjie Zheng; Jinsong Zhang; Longlong Jiang; Rui Li; Shaojin Wang (Journal of Food Engineering, 2026)

Deciphering the effects of cascade reservoirs on phytoplankton communities in a karst river: Importance of super-large reservoirs - Jiang Wu; Xiao-Nan Wu; Xiao-Hui Zhao; Xu Han; En-Hang Liang; Rui An; Jia-Ju Liu; Wei-Ling Sun; Nan Xu; Ting Wang (Journal of Environmental Management, 2026)

Photocatalytic carbon dots for food-borne hazards: Antimicrobial and degradation mechanisms and applications in the food industry - Dangfeng Wang; Wangqing Jiang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Hongyan Guo; Fangchao Cui; Xuepeng Li; Tingting Li; Jianrong Li (Food Research International, 2026)

Single-atom Fe engineered-PANI/AC/MXene composite flow electrode for sustainable water desalination and electroplating wastewater treatment - Rui Chen; Yuzhan Luo; Hui Wang; Youyu Tian; Zhiqun Xie; Hui Wang; Zhiwei Jiang; Anqi Wang; Kai Yan; Zongsu Wei (Chemical Engineering Journal, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

Spatial aggregation trends of cultivated land quality and landscape patterns: A remote sensing analysis - Mengmeng Tang; Wenlong Cheng; Zhengbao Gao; Fahui Jiang; Shang Han; Danyang Xu; Rongyan Bu; Shan Tang; Rui Zhu; Min Li; Hui Wang; Changai Lu; et al. (Applied Soil Ecology, 2026)

A near-infrared hemicyanine-derived fluorescent probe for sulfite detection in biomedical investigate - Kai Wang; Dan-Xian Cai; Hao-Xiang Jiang; Zi-Rui Luo; Hong-Rui Zhan (Analytica Chimica Acta, 2026)

Dielectric heating technology assisted for multi-objective processing of agricultural products: research progress, challenges, and future perspectives - Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Longlong Jiang; Rui Li; Shaojin Wang (Critical Reviews in Food Science and Nutrition, 2025)

Individual plant detection and tracking for agricultural robotics in precision field management - Rui Gao; Yufei Sun; Yaru Chen; Honghua Jiang; Dong Wang; Tangyuan Ning; Kun Wang; Yongliang Qiao (Computers and Electronics in Agriculture, 2025)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Hydrofoil performance optimization based on the Kriging method - Qiaowen Yu; Shigang Wang; Rui Deng; Dapeng Jiang; Bing Zheng; Suzhen Zeng (Ocean Engineering, 2025)

Effects of a diet containing glutamine on the slaughter performance, meat quality, and skeletal muscle fiber types of feed-restricted yaks - Ziqi Yue; Shanpeng Ke; Liyuan Shi; Rui Hu; Zhisheng Wang; Quanhui Peng; Huawei Zou; Jianxin Xiao; Yahui Jiang; Fali Wu; Yiping Tang (Meat Science, 2025)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

Retention-driven water flow regulation: A network perspective - Xuan Jiang; Jinsong Zhao; Zhiwen Cai; Jiating Li; Jian Wang; Ling Wang; Xiao Li; Rui Hao; Shuxia Yu; Zhihua Shi (Journal of Environmental Management, 2025)

All-solid-waste-based non-sintered ceramsite prepared from coal fly ash and dechlorinated municipal solid waste incineration fly ash: performance and hydration mechanisms - Kai Xu; Xinyuan Zhan; Yan Wang; Jie Wang; Rui Deng; Rui Wang; Chen Li; Shui Jiang; Xiaomoli Li; Jingyu Li; Yuxi Zhang (Journal of Environmental Management, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Hierarchical spatiotemporal delivery system reprograms osteoclast subtypes to promote angiogenesis and bone regeneration in steroid-induced osteonecrosis of the rat femoral head - Hongyu Quan; Taiyang Li; Chencan Ren; Yuwei He; Hongkun Xie; Zibo He; Rui Wang; Haibin Ding; Jinbao Li; Shiwu Dong; Hong Jiang (Chemical Engineering Journal, 2025)

A new isopropanol-intermediate mechanism for CO2-assisted propane dehydrogenation over ZIF-derived (GaCe)Ox: Toward propylene synthesis - Yun Yang; Rui Liao; Rulan Pu; Peiting Jiang; Lulu Li; Xuyu Wang; Hongbing Ji (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

How topographic and pedological factors affect vegetation responses to drought: a study from the Qinling Mountains, China - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (CATENA, 2025)

Molecular dynamics simulation-driven focused virtual screening and experimental validation of Fisetin as an inhibitor of Helicobacter pylori HtrA protease - Li Gao; Xianqiong Jiang; Hongtao Duan; Yan Shen; Kui Gu; Kuilong Huang; Yuanqiang Wang; Mao Shu; Rui Zhang; Zhihua Lin (Molecular Diversity, 2025)

CLDN4 promotes ferroptosis and inflammation involving JAK2/STAT3 pathway in acute pancreatitis - Chuanming Zheng; Rui Tao; Zhenjie Wang; Xi Zhang; Hai Jiang; Zhong Ji; Hehe Dou; Zhaohui Du (Functional & Integrative Genomics, 2025)

Transcription factor MAZ activates the transcription of hypomethylated TYMP in ccRCC - Yihan Dong; Xinyu Liu; Jiaxin Li; Tianyu Lin; Rui Wang; Huamao Jiang; Yong Wang; Dan Yue (Functional & Integrative Genomics, 2025)

Injectable Hyaluronic Acid Hydrogels Crosslinked by Structure-engineered Aldehyde-functionalized β-Cyclodextrin Derivatives for Long-term Controlled Voriconazole Delivery - Chao Yang; Meng Xin; Yufu Jiang; Wenqian Wang; Wenhui Li; Junlin Quan; Wancong Zhou; Rui Yuan; Zhe Chen; Depeng Shi; Zhijian Ji; Xingxing Yue; et al. (AAPS PharmSciTech, 2025)

Hyperguanyes A and B, two new PPAPs from the branches and leaves of Hypericum perforatum L. with anti-cholinesterase activities - Yanan Li; Kunling Wang; Rui Liu; Jian Jiang; Donghai Zheng (Natural Product Research, 2025)

Formaldehyde emissions in tanker truck cabins: Observation, deep learning prediction and health risk assessment - Rui Zhang; Dongdong Guo; Ruixiu Jiang; Honglin Cao; Yunjia Wu; Lirong Kou; Meng Wang; Linwei Xi; Yang Liu; Haimei Wang; Jianyin Xiong (Science of The Total Environment, 2025)

Corrigendum to “Studies on the regulation of E3 ubiquitin ligase APC3 and its interacting proteins on the tetraspore formation and release in Gracilariopsis lemaneiformis (Rhodophyta)” [Plant Sci. 356 (July) (2025) 112488] - Qiong Wu; Jingyu Zhang; Min Jiang; Jingru Yin; Lu Wang; Rui Chen; Zhenghong Sui (Plant Science, 2025)

Spatial and temporal variability in molecular characteristics of dissolved organic matter in a large freshwater lake: A case from the Dongting Lake, central China - Rui Xu; Yao Du; Tianming Wu; Xinrui Jiang; Baisong Deng; Mengze Li; Yiqun Gan; Mengjie Song; Shaobo Liao; Rui Zhang; Yanxin Wang (Journal of Hydrology, 2025)

Integrated assessment of chromium exposure risk from agricultural soils using chemical extraction, in vitro simulation, and mouse bioassay - Peng Xiao; Yi Zhou; Pengfei Wang; Rui Li; Shimao Xiong; Xiyan Jiang; Yunpeng Li; Yue Wu; Yuntao Yang; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2025)

Gas permeability characteristics and pore structure evolution of sandstones with high-temperature damage effects - Jiang-Feng Liu; Hong-Yang Ni; Xu Chen; Shi-Jia Ma; Zhi-Peng Wang; Rui-Nian Sun (International Journal of Rock Mechanics and Mining Sciences, 2025)

Na/N doped carbon dot nanozymes with enhanced peroxidase activity for antimicrobial food preservation - Dangfeng Wang; Yifan Hou; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Chemistry, 2025)

Laboratory characterization of VOC evaporative emissions from light-duty plug-in hybrid electric vehicles: Environmental impact comparison with conventional vehicles - Ling Li; Rui Yuan; Wei Hu; Hualong Xu; Pingjiang Lv; Qin Xu; Jun Wang; Xue Jiang; Jianxun Tan; Jianli Yin; Zhenliang Li; Dan Zhang (Environmental Pollution, 2025)

Sequential targeted nanomedicine MPC treats cerebral ischemia-reperfusion injury via neuronal microenvironment reprogramming - Shuya Wang; Ruishi Li; Xiaojing Shi; Tingli Xiong; Wenxuan Zheng; Weimin Qi; Min Liu; Lin Dai; Qian Lin; Rui Huang; Wei Dai; Min Zhou; et al. (Chemical Engineering Journal, 2025)

Optimizing electromagnetic attenuation properties via controlled dielectric polarization in Zn single-atom-decorated polymer-derived SiZnCN ceramics - Hao Deng; Yang Li; Ruihua Chen; Chao Ma; Junpeng Jiang; Daoyang Han; Bingbing Fan; Hailong Wang; Rui Zhang; Gang Shao (Chemical Engineering Journal, 2025)

Enhanced rice phosphorus use efficiency under elevated atmospheric CO2 and its drivers - Haiwei Zhang; Ting Xiao; Zihua Shi; Rui Ren; Yu Jiang; Yanfeng Ding; Songhan Wang (Agriculture, Ecosystems & Environment, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Characteristics and primary controls of coral reef carbonate karstification in the South China Sea since the Miocene - Yang Yang; Kefu Yu; Bin Xiong; Wei Jiang; Shendong Xu; Rui Wang; Tianlai Fan (Frontiers in Marine Science, 2025)
Coral reef karstification plays a vital role in sea-air CO 2 exchange, yet its mechanisms remain unclear. This study employs an 878.22-m coral reef sequence (dating to19.6 Ma) from Well CK2 in the Xisha Islands, South China Sea (SCS), to investigate karstification processes, including their signatures, primary controls, and implications for marine carbonate dissolution in global carbon cycling. Petrological and geochemical analyses of CK2 revel distinct karstification characteristics, including: (1) higher surface porosity 25–30%), with randomly distributed pores and fractures of variable sizes and shapes; (2) yellowish-brown to black impregnations; (3) micritic cements accompanied by well-crystallized mineral crystals, and (4) moderately well-sorted and rounded grains. Geochemical signatures show elevated 8787 Sr/ 86 Sr, Mn content, and Mn/Sr ratios, coupled with depleted δ¹³C, δ 18 O and Sr content. These features collectively indicate that karstification in CK2 was dominated by non-selective dissolution and recrystallization processes, principally occurring at the mixing zone in meteoric water systems during prolonged subaerial exposure. Karstification signatures varied across geological epochs, implying different controlling mechanisms. Late Miocene (12.6–10.2 Ma), driven by sustained sea-level fall, exhibited an extreme 87 Sr/ 86 Sr shift and severe erosion. Pleistocene (2.2–1.8, 1.1–0.89, 0.29 and 0.2 Ma), influenced by frequent sea-level fluctuations and warm, humid environments linked to glacial-interglacial cycle and Asian monsoon, displayed the highest surface porosity (15–40%, mean 25%), ochre to tawny impregnations, and micritized cements, along with negative δ¹³C-δ 18 O and elevated 87 Sr/ 86 Sr and Mn/Sr ratios. In contrast, the Middle Miocene Climatic Optimum (16.6–16 Ma) lacked typical karst characteristics but comprised of well-rounded and sorted coral gravels, suggesting reef-building organisms mediate karstification via substrate architecture. These findings demonstrate that sea-level changes and climate conditions control coral reef karstification intensity. Concurrently, dissolution during karstification may significantly modify ocean alkalinity and dissolved inorganic carbon, with potential feedback on carbon cycling in future climate scenarios.

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Inverse design of three-dimensional electrocatalytic oxidation process for water purification via machine learning and DFT-based descriptors - Linjin Li; Qiyao Wang; Yaoze Wang; Guangfei Qu; Yingying Cai; Rui Xu; Ming Jiang; Nanqi Ren (Process Safety and Environmental Protection, 2025)

Airborne bioaerosol transmission in hospital waiting corridor: Characteristic, exposure risk and evaluation of prevention strategies - Zhijian Liu; Duo Cai; Chenxing Hu; Lei Jiang; Yongxin Wang; Lina Hu; Rui Rong; Shiyue Li; Jingwei Liu; Jiajun Feng (Journal of Hazardous Materials, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Sulfamethazine degradation via PMS activated by Co-Cu catalyst supported on modified geopolymer - Jiayin Liu; Rui Yang; Qi Jiang; Shaobo Chen; Menghao Fang; Shuguang Wang; Zhongjun Xu (Journal of Environmental Chemical Engineering, 2025)

Influence and mechanism of polyethylene microplastics on antibiotic resistance genes and microbial community in sludge composting process - Jie Yang; Rui Jiang; Yingchun Li; Weijian Liu; Mengmeng Wang; Peng Ren (Journal of Environmental Chemical Engineering, 2025)

Laser-structured bamboo-graphene bilayer evaporator for solar-driven, scalable, and salt-resistant water purification - Liangjuan Jiang; Rui Dang; Xiaoxue Fan; Zhaolan Wang; Shuyu Hou; Zheng Zhang; Dun Wu; Dong Wang; Zheng Cao; Chunlin Liu; Junfeng Cheng (Journal of Environmental Chemical Engineering, 2025)

The organic matrix: An in-depth review of kerogen and its significance - Kouqi Liu; Hongyan Qi; Zhizhong Wang; Bo Liu; Yamin Wang; Zhengchen Zhang; Hong Zhang; Rui Yang; Liangliang Jiang; Mehdi Ostadhassan (Fuel, 2025)

Scale effects on buffeting response of long-span bridges - Yi Su; Mingshui Li; Jin Di; Rui Sun; Ming Li; Fengjiang Qin; Yan Jiang; Jie Wang (Engineering Structures, 2025)

Aramid nanofiber-reinforced MXene fibers for flexible supercapacitors - Yiwen Gan; Ningjing Song; Jiaxin Quan; Ting Ding; Xupu Jiang; Rui Wang; Wujun Ma; Chuntao Lan; Min Li; Meifang Zhu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Versatile, cost-effective and highly-multiplex nucleic acid detection through the Engineered Hairpin Cleavage Amplification (EHCA) strategy - Zhaocheng Liu; Rui Zhang; Yi Zhang; Huijun Mu; Xinyi Jiang; Jian Zou; Tingting Wang; Ying Yin (Chemical Engineering Journal, 2025)

Ratiometric core/shell Nanosensors for Simultaneously Measuring Mitochondrial ATP Production and Oxygen Consumption in Living Cells - Rui Jiang; Ying Lian; Enlai Yang; Ying Xu; Jiahao Liang; Yang Yang; Nianhong Wang; Xu-dong Wang (Phenomics, 2025)

BDNF Alleviates Noise-Induced Cochlear Synaptopathy Through Inhibition of Autophagy - Fei Wang; Qianru Yu; Yangtuo Luo; Rui Guo; Liyuan Wu; Xinyu Song; Yang Li; Shuna Li; Ke Liu; Xuejun Jiang (Molecular Neurobiology, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

Physiological and morphological modulations alleviate the ecotoxicity effects of microplastics on microalgae - Jia Liang; Xiao Tan; Zhipeng Duan; Rui Zhu; Jian Gao; Jiang Huang; Lv Wang (Process Safety and Environmental Protection, 2025)

Personnel exposure studies to multi-source diffusion of bioaerosols under biosafety laboratory - Level 2 plus operating conditions - Yongxin Wang; Zhijian Liu; Chuan Jiang; Lei Jiang; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Unlocking the bioremediation potential of adapted Desulfovibrio desulfuricans in acidic low-temperature U-contaminated groundwater - Lei Zhou; Nan Bai; Rui Xiao; Zhendong Yang; Guoping Jiang; Huaqun Yin; Yujie Wang; Liangzhi Li; Delong Meng; Zhenghua Liu (Journal of Environmental Sciences, 2025)

Physicochemical characteristics, flavor profile, and microbial community of commercial traditional fermented chili pepper in Guizhou (Zao pepper) - Xijuan Zhang; Pei Gao; Qixing Jiang; Yongjun Wu; Shuhan Yang; Xiaojing Zhang; Rui Cao; Jing Wang; Min Jiang; Shaoquan Liu; Peipei Yu; Fang Yang; et al. (Food Bioscience, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Customized microbial inoculants enhance rhizosheath functionality and drive ecosystem restoration in desertified grasslands - Qiqi Han; Weimeng Liu; Yingjie Jiang; Pengyuan Yang; Zixuan Wang; Ziyuan Yan; Zhuo Zhang; Rui Xu; Hui Tang; Guixia Liu (Plant and Soil, 2025)

Root-soil-microbe interactions mediate phosphorus and iron uptake from lithium iron phosphate nanomaterials - Yaqi Jiang; Yi Sun; Changcheng An; Pingfan Zhou; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Applied Soil Ecology, 2025)

Two new diarylheptanoids from Curcuma kwangsiensis rhizomes - Shuo-Guo Li; Le Deng; Qiu-Fang Chen; Rui Yang; Cao-Min Zou; Shu-Mei Wang; Meng-Hua Wu; Jiang Meng (Natural Product Research, 2025)

Nested MPI-CWRF dynamical downscaling and future projections of summer extreme precipitation changes in China - Huan Li; Fengxue Qiao; Nan Wei; Haoran Xu; Rui Wang; Fulin Jiang; Guimin Lou; Jia Zhao; Qingyu Yang (Frontiers of Earth Science, 2025)

Bifunctional collagen fibers-based porous material for integrated purification of oily seawater - Xiaoliang Ding; Yejun Yan; Zhexuan Gu; Rui Shi; Yaxin Wang; Guoxin Xu; Zhijun Hu; Zhicheng Jiang (Journal of Hazardous Materials, 2025)

Improvement of nutritional value of cotton residue by solid state fermentation - Duoting Wu; Xiurong Liang; Rui Hu; Zhisheng Wang; Huawei Zou; Fali Wu; Hui Li; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Hongbo Li; Zhenyong Zhou (Journal of Environmental Chemical Engineering, 2025)

Coupled mutual feedback and interaction mechanisms among the geological environment, ecological environment and human activities in the Qinling Mountains - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (Science China Earth Sciences, 2025)

Drivers of ecosystem service trade-off changes in different climate zones: a case study of the Sichuan–Yunnan–Loess plateau ecological shelter, China - Hao-Rui Li; Shuai Ma; Ming Zhang; Yun-Ke Yin; Hai-Bo Hu; Liang-Jie Wang; Jiang Jiang (Environment, Development and Sustainability, 2025)

Studies on the regulation of E3 ubiquitin ligase APC3 and its interacting proteins on the tetraspore formation and release in Gracilariopsis lemaneiformis (Rhodophyta) - Qiong Wu; Jingyu Zhang; Min Jiang; Jingru Yin; Lu Wang; Rui Chen; Zhenghong Sui (Plant Science, 2025)

Morphology-engineered porous flower-like CoNi-LDO with oxygen vacancies for the production of aromatic amines through waste H2S - Weiping Jiang; Rui Huang; Xiaohai Zheng; Ganchang Lei; Shiping Wang; Lijuan Shen; Yingying Zhan; Lilong Jiang (Journal of Hazardous Materials, 2025)

Aluminum and microplastic release from reflective agricultural films disrupt microbial communities and functions in soil - Kai Wang; Markus Flury; Yakov Kuzyakov; Hao Zhang; Wei Zhu; Rui Jiang (Journal of Hazardous Materials, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

Contrasting Effects of Warming and Nitrogen Addition on soil CO2 Emission in a Semi-Arid Grassland on the Loess Plateau of China - Mingfeng Jiang; Zhun Tian; Rui Wang; Zihan Sun; Yang Peng; Chao Fang (Water, Air, & Soil Pollution, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Decaying logs and gap positions jointly maintain the structure and function of soil invertebrate community in a subalpine forest - Yurui Jiang; Zhuang Wang; Rui Cao; Qin Wang; Weizhong Li; Wanqin Yang (Plant and Soil, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Impact of lithofacies categories on inflection-point behaviors in micro-nano pore-structure evolution: Implications for differential reservoir-forming mechanisms and “sweet-spot intervals” identification for marine gas shales - Wei Yang; Rui Yang; Min Wang; Shujing Bao; Leilei Yang; Haodong Hou; Yan Song; Zhenxue Jiang; Ke Miao; Liang Xu (Marine and Petroleum Geology, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Cement-mortar lining failure and metal release caused by electrochemical corrosion of ductile iron pipes in drinking water distribution systems - Hao Guo; Rui Wang; Menghan Jiang; Yimei Tian; Yapeng Jin; Weigao Zhao; Chenwan Wang; Jianhua Yin (Journal of Environmental Sciences, 2025)

Transport of cyclic volatile methylsiloxanes in residence due to the use of personal care products - Ruixiu Jiang; Rui Zhang; Haimei Wang; Jianyin Xiong (Environmental Research, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Highly sensitive and wash-free human serum albumin detection based on filtration-to-enhancement compound microsphere system - Chen Yang; Xin Zhang; Minjing Mo; Guoqing He; Menglu Gao; Tao Jiang; Yihan Ma; Xiaotong Si; Rui You; Fubing Wang; Yi Yang (Chemical Engineering Journal, 2025)

Synergistic adsorption-catalysis system based on the advanced oxidation technology of single-atom MOFs: Selective degradation and contribution to different ionization potential pollutants - Si-Han Zhou; Rui-Dong Wang; Yun Yang; AiJin Xiao; Xuejun Pan; Feng-zhi Jiang (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Growth monitoring of rapeseed seedlings in multiple growth stages based on low-altitude remote sensing and semantic segmentation - Fanguo Zeng; Rui Wang; Youming Jiang; Zhendong Liu; Youchun Ding; Wanjing Dong; Chunbao Xu; Dongjing Zhang; Jun Wang (Computers and Electronics in Agriculture, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Holocene coral reef carbonate REY geochemistry during the neomorphism from aragonite to calcite: A case study in the South China Sea - Wei Jiang; Yuwen Xiao; Kefu Yu; Rui Wang; Shendong Xu; Ning Guo; Tingwu Gu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Mn-oxidizing microalgae and woodchip-denitrifying bioreactor system for recovering manganese and removing nitrogen from electrolytic manganese metal industrial tailwater - Xinyue Gong; Qin Peng; Ruixin Jiang; Na Yang; Cijun Xing; Rui Wang (Journal of Hazardous Materials, 2025)

Different effects of bio/non-degradable microplastics on sewage sludge compost performance: Focusing on antibiotic resistance genes, virulence factors and key metabolic functions - Xiangyu Liu; Huiyue Li; Jie Yang; Shen Yan; Yufei Zhou; Rui Jiang; Renhe Li; Mengmeng Wang; Peng Ren (Journal of Hazardous Materials, 2025)

Computer simulation analysis to improve radio frequency heating uniformity of multi-component rice samples by screening of sample structure - Yingqi Tian; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

In-field degradation of polybutylene adipate-co-terephthalate (PBAT) films, microplastic formation, and impacts on soil health - Kai Wang; Markus Flury; Shiyan Sun; Junling Cai; Aihua Zhang; Qiang Li; Rui Jiang (Environmental Research, 2025)

Harnessing waste H2S for aromatic amines production over porous K2MoSX/SiO2 catalyst - Rui Huang; Weiping Jiang; Xiaohai Zheng; Ganchang Lei; Shiping Wang; Shijing Liang; Lijuan Shen; Yingying Zhan; Lilong Jiang (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Reclaimed-land subsidence mechanism analysis and evolution prediction of Tianjin Binhai New Area, China based on time-series InSAR observations - Rui Zhang; Anmengyun Liu; Tianyu Wang; Yunjie Yang; Jichao Lv; Hang Jiang; Kangyi Chen; Wenfei Mao (Advances in Space Research, 2025)

The potential of golden apple snail (Pomacea canaliculata) meat meal as an alternative protein source for juvenile Chinese mitten crab (Eriocheir sinensis) - Wenxiang Yao; Chunyan Zhang; Rui Jia; Sitong Zhao; Weibo Jiang; Guoan Hua; Sizhe Zhao; Apeng Lin; Jianguo Wang; Quan Wang (Frontiers in Marine Science, 2025)
This study investigated the effects of replacing dietary fish meal (FM) with golden apple snail ( Pomacea canaliculata ) meat meal (PCM) on growth performance, non-specific immunity and intestinal health of juvenile Chinese mitten crab ( Eriocheir sinensis ). Four hundred juvenile Chinese mitten crabs (2.39 ± 0.03) g were randomly distributed into five groups in quadruplicate (20 crabs per tank), and each group was fed with diets that replaced FM with PCM at 0% (FM-20, containing 200 g/kg FM), 25% (FM-15), 50% (FM-10), 75% (FM-5), and 100% (FM-0) for 8 weeks, respectively. The results showed that the growth, whole body composition, digestive enzyme activities, antioxidant performance, non-specific immunity, intestinal histology and microbiota composition of FM-15 and FM-10 groups all reached the same level as the FM-20 group ( P > 0.05). While the replacement ratio reached 75%, the FCR was significantly increased and the peritrophic membrane thickness was significantly decreased ( P< 0.05). When 100% FM was replaced, significantly decreased the growth performance, serum antioxidant and immune enzyme activities, mid-intestine folds height, width and the peritrophic membrane thickness ( P< 0.05), and significantly increased the abundance of intestinal harmful bacteria Vibrio ( P< 0.05). In conclusion, PCM can effectively replace 50% dietary FM (100 g/kg) without negative effects on the growth performance, intestinal health, serum immune, and antioxidant indexes of juvenile E. sinensis .

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Undrained permanent deformation characteristics of Yellow River silt under one-way cyclic loads - Yuke Wang; Hao Chen; Yujie Xue; Rui Jiang; Xiang Yu; Xiaoying Lin (Marine Georesources & Geotechnology, 2025)

Identification and fungicide sensitivity of Fusarium oxysporum, the cause of Fusarium wilt on Codonopsis pilosula in Shanxi Province (Lu Dangshen), China - Yan Wang; Dainan Hao; Haozhe Jiang; Zhaoxiong Fei; Rui Zhao; Jiaxin Gao; Guangxin Li; Chunwei Wang (Crop Protection, 2025)

Selenium doped CeO2 catalysts efficiently activated H2O2 for norfloxacin degradation: Oxygen vacancies mediated electron transfer processes - Zhengkai Hao; Lipeng Jiang; Rui Tan; Yaxin Wang; Bowen Deng; Xinrui Yan; Dengqian Chen; Dongxue Cao; Limei Chen; Dongdong Liu (Journal of Environmental Chemical Engineering, 2025)

A cascade control strategy for electromagnetic capacity control system of reciprocating compressor - Rui Zhang; Yao Wang; Yidan Zhang; Degeng Zhao; Jinjie Zhang; Zhinong Jiang; Ting Lei; Mingze Zhou (International Journal of Refrigeration, 2025)

Corrigendum to “Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation” [Food Research International 203 (2025) 115792] - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Novel nonmetallic acidic molten salt anode with high lithium storage capacity and Proper voltage platform for lithium-ion batteries - Yiting Wang; Jiali Chai; Longzhen Wang; Zhiyuan Chen; Ning Han; Bohejin Tang; Yichuan Rui; Lei Jiang (Chemical Engineering Journal, 2025)

Comparative chloroplast genome analysis of the medicinal species in Rubus: Insights into genomic characterization and phylogenetic relationships - Jiayu Jiang; Rui Tian; Ruolan Wang; Shuang Wang; Dequan Zhang (Plant Systematics and Evolution, 2025)

Association between Low Serum Testosterone Levels and All-cause Mortality in Patients With Cardiovascular Disease: A Study Based on the NHANES Database - Rui Jiang; Yongchen Wang (Cardiovascular Toxicology, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Structure, sources, functional mechanisms, and applications of bioactive glycopeptides in food: A comprehensive review - Dangfeng Wang; Benyou Zhang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Trends in Food Science & Technology, 2025)

RNA interference-mediated silencing of GNBP2 reduces the immunity of stored pest Tribolium castaneum against bacteria - Jingxiu Bi; Xiangjun Ma; Yuying Jiang; Pingxiang Liu; Rui Gao; Tong Zhao; Xuexia Yuan; Haining Hao; Bin Li; Yutao Wang (Pesticide Biochemistry and Physiology, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Migration and distribution of thallium related with lead-zinc smelting enterprises from raw materials to soil: In-situ insight using diffusive gradients in thin-films - Wenhao Wang; Siwei Deng; Jiang Yu; Yi Wu; Wenjuan Feng; Qin Fan; Rui Zhou; Peirou Li; Wei Deng; Zhi Huang; Jie Yu; Weiwei Zhu (Environmental Pollution, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

CircTBCK protects against osteoarthritis by regulating extracellular matrix and autophagy - Wei Wang; Yuzhe Sun; Peng Tang; Rui Zhang; Yufeng Jiang; Hongwei Min; Chen Gao (Human Cell, 2025)
Osteoarthritis (OA) is a widespread chronic bone and joint disease for which there is currently no effective preventive or therapeutic treatment. Accumulating evidence indicates that circular RNAs (circRNAs), a class of noncoding RNAs, play critical roles in OA. Therefore, in this study, we aimed to reveal an unexplored circTBCK and elucidate its mechanism of action in the pathological process of OA. The different expression of circTBCK was obtained both in vitro and in vivo. In the in vivo model, mice were induced via destabilization of the medial meniscus (DMM) surgery, while in vitro model, mouse cells like primary chondrocytes of newborn mice and ATDC5 cell line were treated with IL-1β treatment (10 ng/mL for 24 h). The level of circTBCK was examined by quantitative real-time polymerase chain reaction (qRT-PCR). After circTBCK was overexpressed or knocked down, IL-1β treatment was performed, and then, chondrocyte viability was detected via a Cell Counting Kit-8 (CCK-8) assay at 0, 24, 48, or 72 h. To assess type II collagen (Collagen II) expression, immunofluorescence (IF) analysis was used. The levels of mRNAs and proteins related to proliferation, the extracellular matrix (ECM) and autophagy were determined by qRT-PCR and Western blotting. Compared with OA treatment, primary chondrocytes with treatment of both circTBCK overexpression and IL-1βincreased the expression of anabolic factors—Collagen II and SRY-box transcription factor 9 (SOX9), proliferation-related molecules—Ki-67 and proliferating cell nuclear antigen (PCNA), and autophagy-related molecules—Microtubule-associated protein 1 light chain 3 (LC3), B-cell lymphoma 1 (Bcl1), and autophagy-related 5 (Atg5) and decreased Sequestosome 1 (SQSTM1 or P62). In contrast, knockdown of circTBCK aggravated the chondrocyte degeneration induced by IL-1β. Overall, our findings suggest that circTBCK, an unexplored circRNA, could regulate autophagy, proliferation, and the extracellular matrix (ECM) to mitigate the development of OA, suggesting a possible target for OA prevention and therapy.

Sequential decline in cyanobacterial, total prokaryotic, and eukaryotic responses to backward flow in a river connected to Lake Taihu - Jun Zuo; Siyu Yang; Hans-Peter Grossart; Peng Xiao; He Zhang; Rui Sun; Guoyou Li; Haoran Jiang; Qihang Zhao; Meng Jiao; Yao Cheng; Zeshuang Wang; et al. (Water Research, 2025)

Chicken adipose tissue is differentially involved in primary and secondary regional immune response to NDV through miR-20a-5p-NR4A3 pathway - Yi Jiang; Rui Zhang; Xinxin Xu; Xiangnan Wang; Yufei Tian; Wei Zhang; Xiaoli Ma; Chaolai Man (Veterinary Immunology and Immunopathology, 2025)

Enhanced selenite removal performance of zero valent iron-biochar composite by in situ formed Fe2SiO4 during ash-rich biomass pyrolysis - Shunfeng Jiang; Rui Zhang; Zhiquan Wang; Min Zhao; Xiangyong Zheng (Process Safety and Environmental Protection, 2025)

Severity and risk to inhalation of pathogen-laden aerosol in large public spaces: Insights from fangcang shelter hospitals under multi-location release - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jingwei Liu (Journal of Hazardous Materials, 2025)

Monitor and classify dough based on color image with deep learning - Bryan Gilbert Murengami; Xudong Jing; Hanhui Jiang; Xiaojuan Liu; Wulan Mao; Yuedan Li; Xueyong Chen; Shaojin Wang; Rui Li; Longsheng Fu (Journal of Food Engineering, 2025)

Relative contributions of climate and grazing to forage supply in the Yellow River source area - Suizi Wang; Jiangwen Fan; Miaomiao Wang; Rui Tang; Nan-Ji Jiang (Journal of Environmental Management, 2025)

A TiO2/ZnO (nanoparticle/quantum dot) heterojunction with strong interfacial coupling for ultrasensitive SERS sensing of antibiotic residues in environment (water and soil) and their efficient degradation - Yimin Tang; Xuewei Zhang; Rui Wang; Huizhu Zhang; Libin Yang; Xin Jiang; Bing Zhao (Journal of Environmental Chemical Engineering, 2025)

Analytical solutions of two-liner tunnels constructed in time-dependent plastic rocks considering loading-unloading stress paths - Hua-ning Wang; Qian Liu; Fei Song; Rui-cong Fu; Ming-jing Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

A novel g-C3N4/TiO2 heterojunction for ultrasensitive detection of bisphenol A residues - Xin Jiang; Han Jiang; Yimin Tang; Rui Wang; Wenxue Wang; Libin Yang; Bing Zhao (Food Chemistry, 2025)

Graphene bilayer film responsive to ultraviolet, humidity, and temperature - Lin Wang; Tao Wang; Yalong Li; Yi Huang; Rui Li; Jing Zhang; Jie Jiang; Pei Li; Yan Fan; Liang Chen (Chemical Engineering Journal, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

Impact of corporate environmental responsibility on green innovation efficiency: evidence from Chinese a-share listed companies - Feng Wang; Xiaoxuan Bai; Yifan Zhang; Rui Ling; Hongfei Jiang (Environment, Development and Sustainability, 2025)

Ecological economic resilience in China: systematic performances, structural characteristics and evolutionary predictions - Kexin Wang; Rui Ding; Wenqian Xiao; Juan Liang; Lina Peng; Shuyue Jiang (Environment, Development and Sustainability, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Susceptibility and risk to inhalation of pathogen-laden aerosol in large public spaces: Evidence from Fangcang Shelter Hospitals under multiple ventilation rates - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jiaqi Chu; Jingwei Liu (Sustainable Cities and Society, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Laser-induced ZnxMnOx-rGO-C@LIG materials doped with diesel distillate for Zn-ion hybrid supercapacitors - Yuxia Wang; Hu Zou; Zhong Qi; Siyu Yang; Wenlong Jiang; Rui Zhang; Zhengchun Yang; Junjun Shi; Jie He; Peng Pan; Huayi Li (Chemical Engineering Journal, 2025)

Readily recyclable, degradable, stretchable, highly conductive, anti-freezing and anti-drying glycerohydrogel for triboelectric nanogenerator - Sihan Jiang; Yang Wang; Meiqin Tian; Haiyang Zhang; Rui Wang; Haokun Yan; Hao Tan; Rasoul Esmaeely Neisiany; Wei Sun; Zhengwei You (Chemical Engineering Journal, 2025)

Eliminating bacterial endotoxins and associated inhalation hazards in reclaimed water via ultraviolet/ferrate combination disinfection - Muhan Sun; Xiaoxu Jiang; Rui Liu; Deqin Kong; Hao Wu; Zhao Wang; Gang Zheng; Chongmiao Zhang; Weihua Yu (Chemical Engineering Journal, 2025)

Volatile organic compounds from Stenotrophomonas geniculata J-0 as potential biofumigants manage bulb rot caused by Fusarium oxysporum in postharvest Lanzhou lily - Lijun Ling; Rui Yue; Yuanyuan Wang; Lijun Feng; Ling Yang; Yao Li; Rongxiu Mo; Wenyue Zhang; Fanjin Kong; Yijuan Jiang; Yongpeng Zhou (World Journal of Microbiology and Biotechnology, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Recycled lithium battery nanomaterials as a sustainable nanofertilizer: Reduced peanut allergenicity and improved seed quality - Yaqi Jiang; Yi Sun; Pingfan Zhou; Guikai Zhu; Qibin Wang; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Physical mechanism-based simulation methods for soil and ground heat flux from observations at multi-sites - Zhaofei Liu; Dong Jiang; Rui Wang; Mengmeng Hao; Xingxing Zhang (Journal of Hydrology, 2024)

Xenobiotic metabolism activity of gut microbiota from six marine species: Combined taxonomic, metagenomic, and in vitro transformation analysis - Siqi Zhang; Rui Hou; Yuchen Wang; Qianyi Huang; Lang Lin; Hengxiang Li; Shan Liu; Zhijian Jiang; Xiaoping Huang; Xiangrong Xu (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

The effect of LuxR solo EvgA on the spoilage potential of Pseudomonas fluorescens - Dangfeng Wang; Benyou Zhang; Yunting Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Fangchao Cui; Tingting Li; Jianrong Li (Food Bioscience, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Curcumin protects porcine granulosa cells and mouse ovary against reproductive toxicity of aflatoxin B1 via PI3K/AKT signaling pathway - Sihong Li; Rui Li; Jun Jiang; Lu Liu; Xiang Ma; Tao Wang; Lili Zhao; Weifen Li; Dong Niu (Environmental Pollution, 2024)

Iron-doped diesel exhaust early-in-life inhalation-induced cardiopulmonary toxicity in chicken embryo: Roles of ferroptosis and acyl hydrocarbon signaling - Siyi Wang; Xinxian Gong; Junhua Yuan; Jing Huang; Rui Zhao; Jing Ji; Meinan Wang; Xiaoyu Shi; Wenya Xin; Yuxu Zhong; Yuxin Zheng; Qixiao Jiang (Environmental Pollution, 2024)

Three-dimensional discrete element simulation on mechanical response and failure characteristics of composite rock under triaxial unloading condition - Sheng-Qi Yang; Yu Song; Shi-Gui Du; Rui Yong; Su-Sheng Wang; Yun-Jin Hu; Jiang Zhao (Computers and Geotechnics, 2024)

Enhancing hydrothermal stability of NH3-SCR reaction over Cu-SSZ-52 catalyst by increasing Si/Al ratio - Xiangqiong Jiang; Zhifeng Zeng; Dongdong Chen; Yuyan Yao; Yang Zhang; Shuangjia Wang; Rui Li; Jiuxing Jiang (Chemical Engineering Journal, 2024)

A multimodal classification method: Cow behavior pattern classification with improved EdgeNeXt using an inertial measurement unit - Yingqi Peng; Yingxi Chen; Yuxiang Yang; Meiqi Liu; Rui Hu; Huawei Zou; Jianxin Xiao; Yahui Jiang; Zhisheng Wang; Lijia Xu (Computers and Electronics in Agriculture, 2024)

Ancient genomic time transect unravels the population dynamics of Neolithic middle Yellow River farmers - Shiwei Li; Rui Wang; Hao Ma; Zheng Tu; Limin Qiu; Haodong Chen; Li Jiang; Yuezu Geng; Hai Liu; Jifeng Wang; Qu Shen; Li Jin; et al. (Science Bulletin, 2024)

Dynamic nonparametric modeling of sail-assisted ship maneuvering motion based on GWO-KELM - Haoyang Zhao; Lianzhong Huang; Ranqi Ma; Kai Wang; Tiancheng Wang; Zhang Ruan; Rui Zhang; Baoshen Jiang; Xiaowu Li; Jianyi Wu (Ocean Engineering, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

A photosensitive modification of recombinant Salmonella carrying shRNA-PD-L1 promotes host immunity against poorly immunogenic tumors - Jiaying Yang; Mei Yang; Qi Wang; Qian Luo; Yingtong Wang; Jicheng Sun; Jixuan Liu; Jiasi Chen; Juanjuan Mao; Hailin Yin; Dhan V. Kalvakolanu; Baofeng Guo; et al. (Chemical Engineering Journal, 2024)

Multifunctional visible light photocatalytic carbon dots synergize with reactive oxygen species for anti-quorum sensing and anti-bacteria for salmon preservation - Fangchao Cui; Xin Wang; Dangfeng Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Yilin Lu; Xuepeng Li; Tingting Li; et al. (Chemical Engineering Journal, 2024)

Effects and fate of metal-based engineered nanomaterials in soil ecosystem: A review - Qibin WANG; Peng ZHANG; Weichen ZHAO; Shakoor NOMAN; Adeel MUHAMMAD; Guikai ZHU; Yi SUN; Quanlong WANG; Yaqi JIANG; Yukui RUI (Pedosphere, 2024)

Enhancing soil gross nitrogen transformation through regulation of microbial nitrogen-cycling genes by biodegradable microplastics - Hao Zhang; Wei Zhu; Jinbo Zhang; Christoph Müller; Lifen Wang; Rui Jiang (Journal of Hazardous Materials, 2024)

Multifunctional Ni-MOF (3D) with N-rich structures for self-generated reactive oxygen species and enhanced electron transfer for synergistic degradation of organic pollutants and removal of Hg(II) - Si-Han Zhou; Rui-Dong Wang; Yun Yang; Hui-ying Li; Li-jun Luo; Feng-zhi Jiang (Journal of Cleaner Production, 2024)

Nano Fe3O4 improved the electron donating capacity of dissolved organic matter during sludge composting - Liu Chen; Zeyu Zhang; Rui Yang; Xiaojie Wang; Jieyu Yu; Hong Jiang; Wenjie Zhang; Beidou Xi; Xiaojie Sun; Ningjie Li (Journal of Environmental Management, 2024)

Developing a radio frequency-hot air spouting treatment for efficient dehydration of carrot cubes: Evaluation of the heating and moisture distribution uniformity - Junjie Zheng; Xin Ye; Longlong Jiang; Xiaojiang Wang; Mengge Li; Yingqi Tian; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Continuous production of pure formic acid solution from CO2 hydrogenation at room temperature via amine-functionalized PdMn nano-alloy - Xiuqin Ci; Dong Zhai; Rui Tu; Xiaoju Li; Shuchao Jiang; Xinbo Wang; Weiqiao Deng; Guoqing Ren (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Current status and impact of the Young Scientist Foundation of the National Natural Science Foundation on Chinese young scholars in cardiovascular research - Fei Gao; Zhenzhen Chen; Wendong Li; Hujun Jiang; Rui Wang (Science China Life Sciences, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Effects of Different Concentrations of Weak Acid Fracturing Fluid on the Microstructure of Coal - Gan Rui; Zuo Shaojie; Si Junting; Liu Chengwei; Tian Feng; Jiang Zhizhong; Wang Changwei; Peng Shouqing; Xu Zhiyuan (Natural Resources Research, 2024)

Bentonite/Sesbania Gum Hydrogel for Effective Removal of Cationic Dyes: Network Structure Construction and the Role of Multiple Hydroxyl and Carboxyl Adsorption Sites - Luying Jiang; Sishan Yu; Jingwei Zhang; Zisong Xu; Rui Tang; Yinlong Wang; Ke Liang; Chen Zhai; Zhangfa Tong; Hanbing Zhang (International Journal of Environmental Research, 2024)

A dynamic snow depth retrieval model based on time-series clustering optimization for GPS-IR - Tianyu Wang; Rui Zhang; Yunjie Yang; Anmengyun Liu; Yao Jiang; Jichao Lv; Jinsheng Tu; Yunfan Song (Advances in Space Research, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

High-throughput proximal ground crop phenotyping systems – A comprehensive review - Z. Rui; Z. Zhang; M. Zhang; A. Azizi; C. Igathinathane; H. Cen; S. Vougioukas; H. Li; J. Zhang; Y. Jiang; X. Jiao; M. Wang; et al. (Computers and Electronics in Agriculture, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Semi-liquid metal-based highly permeable and adhesive electronic skin inspired by spider web - Rui Guo; Xiaoqing Li; Yingtong Zhou; Yuqi Zhang; Chengjie Jiang; Yang Yu; Qingting Tan; Wenbo Ding; Hongzhang Wang (Science Bulletin, 2024)

TiO2 thermal stress deformation induced to promote photocatalytic CO2 reduction - Yixuan Shen; Kaifeng Gong; Le Chen; Jiafan Wang; Tao Wang; Yuan Gao; Jie Niu; Rui Zhu; Qizhen Liu; Jiang Wu; Ping He (Fuel, 2024)

Impact of long-term conventional and biodegradable film mulching on microplastic abundance, soil structure and organic carbon in a cotton field - Kai Wang; Wei Min; Markus Flury; Anna Gunina; Jun Lv; Qiang Li; Rui Jiang (Environmental Pollution, 2024)

Efficient photocatalytic degradation of 24 imidazolium ionic liquids in an N-ZnO/simulated sunlight irradiation system and its mechanism - Jiaoqin Liu; Jingjing Zhang; Mengye Jia; Rui Ma; Ruijuan Qu; Zunyao Wang; Zhaoguo Liu; Yu Jiang; Haoxiang Zhang; Yujia Bai; Riya Jin; Yina Qiao; et al. (Chemical Engineering Journal, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Correction: Desmoglein-2 Affects Vascular Function in Moyamoya Disease by Interacting with MMP-9 and Influencing PI3K Signaling - Ajun Wang; Nan Li; Nan Zhang; Jian Liu; Tao Yang; Dongxue Li; Changwen Li; Rui Li; Tongcui Jiang; Chengyu Xia (Molecular Neurobiology, 2024)

Ceftriaxone Modulates Ubiquitination of α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid Receptors to Improve Long-Term Potentiation Impairment Induced by Exogenous β-Amyloid in a Glutamate Transporter-1 Dependent Manner - Rui Jiang; Li Li; Bu Wang; Lizhe Liu; Lirong Liu; Xiaohui Xian; Wenbin Li (Molecular Neurobiology, 2024)

Desmoglein-2 Affects Vascular Function in Moyamoya Disease by Interacting with MMP-9 and Influencing PI3K Signaling - Ajun Wang; Nan Li; Nan Zhang; Jian Liu; Tao Yang; Dongxue Li; Changwen Li; Rui Li; Tongcui Jiang; Chengyu Xia (Molecular Neurobiology, 2024)
The pathogenesis and development of Moyamoya disease are still unclear. This study aimed to investigate the effect of desmoglein-2 (DSG2) on Moyamoya disease and determine the inhibitory effect of DSG2 in vascular remodeling in Moyamoya disease. RNA sequencing, immunohistochemistry (IHC), and western blotting were used to detect the expression of DSG2 in the superficial temporal artery (STA) tissues of Moyamoya disease. The association between DSG2 and endothelial cells’ biological activities was investigated by cell counting kit-8 (CCK-8), migration assay, tube formation assay, flow cytometry with Annexin V-FITC/PI staining, and TUNEL apoptotic cell detection kit. Pathways affected by overexpression or knockdown of DSG2 were identified in endothelial cells. The expression of DSG2 in the STA tissues of Moyamoya disease was lower than that in normal controls. Overexpression of DSG2 inhibits the proliferation and migration but promotes apoptosis in endothelial cells, and low DSG2 levels result in impaired angiogenesis. In addition, there was an interaction between DSG2 and MMP-9, and DSG2 acted through the PI3K signaling in endothelial cells. Our results indicate that DSG2 affects PI3K signaling in vascular endothelial cells, and MMP-9 is involved in DSG2-mediated vascular changes in Moyamoya disease.

Adsorption/desorption of enrofloxacin in farmland soil as the effect of pH and coexisting ions: implications for enrofloxacin fate and risk in loess soil - Jiali Wu; Yufeng Jiang; Rui He; Zhewei Liu; Xiaozhen Zhang; Wenjing Wang; Weichen Kong; Gang Wang; Yingqin Wu (Environmental Geochemistry and Health, 2024)

In vivo manufacture and manipulation of CAR-T cells for better druggability - Rui Hou; Xiaoxue Zhang; Xu Wang; Xuan Zhao; Sijin Li; Zhangchun Guan; Jiang Cao; Dan Liu; Junnian Zheng; Ming Shi (Cancer and Metastasis Reviews, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

Spatial distribution of bioaerosols and evaluation of four ventilation method on controlling their diffusion in a typical enhanced biosafety level 2 laboratory - Zhijian Liu; Yongxin Wang; Chuan Jiang; Junzhou He; Rui Rong; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2024)

Developing a spouted bed for combined radio frequency-hot air treatments to improve the heating uniformity in high-moisture carrot cubes - Junjie Zheng; Longlong Jiang; Xin Ye; Xiaojiang Wang; Yingqi Tian; Mengge Li; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Effect of BaTiO3 as a filling material with adjustable dielectric properties on improving the radio frequency heating uniformity in red jujubes - Longlong Jiang; Junjie Zheng; Mengge Li; Yingqi Tian; Xiaojiang Wang; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Developing effective radio frequency drying processes for tiger nuts: Dynamic analysis of moisture state, dielectric properties and quality - Mengge Li; Yingqi Tian; Longlong Jiang; Juanjuan Xu; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Preparation of ternary composite film TiO2/Fe2O3/Ti3C2 for photoelectrocatalytic degradation of organic pollutants and bacterial inactivation in water - Yanping Ma; Jialin Gu; Xinshang Li; Wenquan Zhou; He Wang; Rui Zhang; Jiangang Jiang (Journal of Environmental Chemical Engineering, 2024)

Extended applications of the small-scale radio frequency system for improving the heating performance of multi-component rice - Yingqi Tian; Haibo Yu; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

From characteristics to practical applications of skin temperature in thermal comfort research – A comprehensive review - Jiaqi Zhao; Rui Wang; Yeyu Wu; Chaoyi Zhao; Yun Qi; Sishi Li; Haihua Jiang; Bin Cao (Building and Environment, 2024)

Slide-controlling modes and classification system of the mélange high slopes: insight into a disaster-causing mechanism of the Jinsha River mélange belt in the eastern Tibetan Plateau - Hongfu Zhou; Meng Wang; Jingyi Xue; Rui Li; Jinpeng Hu; Jiang Xing; Tian Fang (Bulletin of Engineering Geology and the Environment, 2024)

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Impact of high-altitude environments on the motion and settling characteristics of wet-mix shotcrete dust in tunnels - Guoliang Zhang; Zhongan Jiang; Xiaocuan Li; Ya Chen; Bin Yang; Mingli Si; Rui Feng; Ming Wang (Tunnelling and Underground Space Technology, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Biodegradable film mulching increases soil microbial network complexity and decreases nitrogen-cycling gene abundance - Hao Zhang; Duntao Shu; Jiaqi Zhang; Xuejun Liu; Kai Wang; Rui Jiang (Science of The Total Environment, 2024)

Recent progress and perspectives on coal dust sources, transport, hazards, and controls in underground mines - Yong Cao; Yang Xiao; Zhen-Ping Wang; Qing-Wei Li; Chi-Min Shu; Xing-Rui Jiang; Shi-Liang Wu (Process Safety and Environmental Protection, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Development and characterization of a bacterial enzyme cascade reaction system for efficient and stable PET degradation - Chengyong Wang; Rui Long; Xiran Lin; Wei Liu; Liying Zhu; Ling Jiang (Journal of Hazardous Materials, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

Oxygen vacancies-promoted removal of COS via catalytic hydrolysis over CuTiO2-δ nanoflowers - Xiaohai Zheng; Rui Huang; Bang Li; Weiping Jiang; Lijuan Shen; Ganchang Lei; Yingying Zhan; Shiping Wang; Lilong Jiang (Chemical Engineering Journal, 2024)

The Association Between the Levels of Oxidative Stress Indicators (MDA, SOD, and GSH) in Seminal Plasma and the Risk of Idiopathic Oligo-asthenotera-tozoospermia: Does Cu or Se Level Alter the Association? - Tao Yin; Xinyu Yue; Qian Li; Xinyu Zhou; Rui Dong; Jiayi Chen; Runtao Zhang; Xin Wang; Shitao He; Tingting Jiang; Fangbiao Tao; Yunxia Cao; et al. (Biological Trace Element Research, 2024)

Thermal parameter identification of concrete dams based on hybrid particle swarm optimization using distributed optical fiber monitoring data - Chi Zhao; Feng Wang; Xinxin Jiang; Rui Song; Ao Zhang; Xueli Liu (Swarm and Evolutionary Computation, 2024)

Sustainable treatment of aquaculture water employing fungi-microalgae consortium: Nutrients removal enhancement, bacterial communities optimization, emerging contaminants elimination, and mechanism analysis - Rui Mi; Xuda Wang; Ying Dong; Shilei Li; Zelong Zhao; Xiaoyan Guan; Jingwei Jiang; Shan Gao; Zhiyu Fu; Zunchun Zhou (Science of The Total Environment, 2024)

Cu-II-directed self-assembly of fullerenols to ameliorate copper stress in maize seedlings - Chenjie Fan; Qingyuan Liang; Yan Wang; Peimei Chen; Jiakai Wu; Qingnan Wu; Shijun Jiang; Yang Zhou; Rui He; Fuju Tai (Science of The Total Environment, 2024)

Decoding the influence of low temperature on biofilm development: The hidden roles of c-di-GMP - Yu-Ting Lin; Yong-Chao Wang; Yi-Mei Xue; Zhen Tong; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden; Can Wang (Science of The Total Environment, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

Developing a combined rotating and air-circulating system for improving radio frequency heating uniformity and controlling Aspergillus in almond kernels - Rui Li; Yu Gao; Junjie Zheng; Mengge Li; Yujun Hao; Longlong Jiang; Shunqin Bai; Dingting Zhou; Juanjuan Xu; Xiaoxi Kou; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Effect of nano zero-valent iron on the anaerobic digestion of food waste: Performance and mechanism - Ruonan Wang; Naif Abdullah Al-Dhabi; Yufeng Jiang; Xiaofeng Dai; Rui Li; Wangwang Tang; Rongbo Guo; Shanfei Fu (Fuel, 2024)

Manipulating cationic ordering toward highly efficient and zero-thermal-quenching cyan photoluminescence - Hongzhi Zhang; Hong Li; Conglin Liu; Hongming Jiang; Junpeng Li; Yuxin Liu; Jiayi He; Rui Wang; Wanbiao Hu; Jing Zhu (Chemical Engineering Journal, 2024)

Stochastic processes shape microbial community assembly in biofilters: Hidden role of rare taxa - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Ye Deng; Yu-Ting Lin; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden (Bioresource Technology, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

Intestinal carcinogenicity screening of environmental pollutants using organoid-based cell transformation assay - Ziwei Wang; Shen Chen; Yuzhi Guo; Rui Zhang; Qi Zhang; Xinhang Jiang; Miao Li; Yue Jiang; Lizhu Ye; Xiaoyu Guo; Chuang Li; Guangtong Zhang; et al. (Archives of Toxicology, 2024)

Evaluating the fracture resistance and drainage difficulty of coal reservoirs using log data - Zhi-di Liu; Bin-rui Yang; Xiao-yan Tang; Wei Wang; Liang Ji; Zhi-hao Jiang (Applied Geophysics, 2024)

Investigation of the effects and mechanisms of manganese-based NMs on rice growth - Yaqi Jiang; Yi Sun; Peng Zhang; Pingfan Zhou; Qibin Wang; Guikai Zhu; Weichen Zhao; Yuanbo Li; Quanlong Wang; Yukui Rui (Environmental Science and Pollution Research, 2024)

Performance enhancement, bacterial communities optimization and emerging pollutants elimination by microalgal-bacterial consortium for treating aquaculture pond sediments - Xuda Wang; Shilei Li; Rui Mi; Ying Dong; Jingwei Jiang; Xiaoyan Guan; Xiaoyue Wang; Bo Ye; Danni Liu; Zhenjun Zhao; Xuewen Gao; Zunchun Zhou (Journal of Environmental Management, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Development of an analytic method for organosulfur compounds in Welsh onion and its use for nutritional quality analysis of five typical varieties in China - Pingxiang Liu; Peng Wu; Jingxiu Bi; Yuying Jiang; Rui Gao; Lei Gao; Yonghua Li; Tong Zhao; Xiao Zhang; Chao Zhang; Yutao Wang (Food Chemistry, 2024)

Synergistic enhancement of phase change materials through three-dimensional porous layered covalent triazine framework/expanded graphite composites for solar energy storage and beyond - Long Geng; Jiapeng Wang; Xulong Yang; Jiaping Jiang; Rui Li; Yabo Yan; Jiateng Zhao; Changhui Liu (Chemical Engineering Journal, 2024)

Impact of remaining roots on soil nematode communities in an aboveground plant functional group removal experiment - Yong Zheng; Ligai Huang; Xue Jiang; Rui Guo; Wenjie Wan; Luping Ye; Tibor A. Drost; Xianhui Zhou; Hui Guo; Juan Zuo; Peng Wang (Plant and Soil, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Brain-Derived Exosomal CircRNAs in Plasma Serve as Diagnostic Biomarkers for Acute Ischemic Stroke - Xinli Jiang; Rui Zhang; Geng Lu; Yu Zhou; Jianfeng Li; Xinrui Jiang; Shuangshuang Gu; Hongwei Liang; Jun Wang (Journal of Neuroimmune Pharmacology, 2024)

Mechanisms of the novel pesticide sodium dodecyl benzene sulfonate in the mitigation of protozoan ciliated pathogens during microalgal cultivation - Gaojingwen Sun; Ruiqi Jia; Yan Zhang; Zhaoji Zhang; Yunlong Wang; Rui Ma; Yaxin Wang; Zhiyang Jiang; Mingjian Liu; Yong Jiang (Marine Pollution Bulletin, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Investigation of pathogen-laden aerosol aerodynamics and ventilation rates on their long-range transmission: A study on the Fangcang shelter hospital - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Shiyue Li; Rui Rong; Zhenyu Liang; Haiyang Liu; Jingwei Liu; Tongliang Wan; Junzhou He (Journal of Cleaner Production, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

TRIM5 as a promising diagnostic biomarker of hepatocellular carcinoma: integrated analysis and experimental validation - Huanxiang Liu; Yuhong Tang; Jiahao Zhang; Gefeng Wu; Qing Peng; Chen Chen; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Guoqing Jiang; Qian Wang; et al. (Functional & Integrative Genomics, 2024)

Feedback regulation of plant secondary metabolism: Applications and challenges - Chuhan Li; Rui Jiang; Xingxing Wang; Zongyou Lv; Wankui Li; Wansheng Chen (Plant Science, 2024)

The transmission of isotopic signals from precipitation to groundwater and its controls: An experimental study with soil cylinders of various soil textures and burial depths in a monsoon region - Ying Jiang; Jie Li; Rui Zuo; Congjian Sun; Yuanzheng Zhai; Lijun Tian; Wei Dai; Shufang Wang; Ziqi Shang; Yulian Liu; Xuan Jiao; Yuxi Xie; et al. (Journal of Hydrology, 2024)

A machine vision-assisted Argonaute-mediated fluorescence biosensor for the detection of viable Salmonella in food without convoluted DNA extraction and amplification procedures - Junpeng Zhao; Minjie Han; Aimin Ma; Feng Jiang; Rui Chen; Yongzhen Dong; Xufeng Wang; Shilong Ruan; Yiping Chen (Journal of Hazardous Materials, 2024)

Energy-efficient trehalose-based polyester nanofiltration membranes for zero-discharge textile wastewater treatment - Xiongwei Luo; Lei Jiang; Rui Zhao; Yue Wang; Xin Xiao; Sabrine Ghazouani; Lihua Yu; Zhaohuan Mai; Hideto Matsuyama; Pengrui Jin (Journal of Hazardous Materials, 2024)

Developing a two-stage strategy in the dehydration treatment of fresh apple slices: Combined freeze and radio frequency-vacuum drying - Xiaojiang Wang; Dingting Zhou; Mengge Li; Junjie Zheng; Longlong Jiang; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

A method to assess industrial paraffin contamination levels in rice and its transferability analysis based on transfer component analysis - Zhentao Wang; Ruidong Wang; Yuhang Chu; Guoqing Chen; Tenghui Lin; Rui Jiang; Jinfeng Wang (Food Chemistry, 2024)

Controlling airborne pathogen within Fangcang shelter hospitals: Aerodynamic analysis of bioaerosols released from various locations through experiment and simulation - Chuan Jiang; Zhijian Liu; Xia Xiao; Haiyang Liu; Junzhou He; Rui Rong; Jingwei Liu; Zhenzhe Huang; Yongxin Wang (Building and Environment, 2024)

Study on the mechanism of Panax notoginseng–Salvia miltiorrhiza herb pair on invigorating blood circulation and eliminating blood stasis by blocking the conversion of arachidonic acid to prostaglandin - Rui Zeng; Yuefan Zhang; Shengtong Shi; Xianqin Long; Haixia Zhang; Min Wang; Jianfeng Shi; Ye Jiang; Bin Chen (Journal of Natural Medicines, 2024)

Simultaneous detection of dual microRNAs related to EV71 using ICP-MS based on metal nanoparticle labeling with hybridization chain reaction - Yuxin Wang; Lijun Shao; Zhigang Zhao; Chao Huang; Yanni Jiao; Dapeng Sun; Rui Liu; Dafeng Jiang; Xibao Gao (Analytica Chimica Acta, 2024)

Capturing spatiotemporal heterogeneity in fertilizer application for better modelling paddy water nitrogen and phosphorus pollution at regional scale - Rui Ren; Huazhan Zhang; Xiang Gao; Housheng Wang; Wei Jiang; Yuhui Wang; Xiaosan Jiang; Zhaofu Li; Haiyan Zhao; Ganghua Li; Yanfeng Ding; Yue Mu (Agriculture, Ecosystems & Environment, 2024)

Deep learning in water protection of resources, environment, and ecology: achievement and challenges - Xiaohua Fu; Jie Jiang; Xie Wu; Lei Huang; Rui Han; Kun Li; Chang Liu; Kallol Roy; Jianyu Chen; Nesma Talaat Abbas Mahmoud; Zhenxing Wang (Environmental Science and Pollution Research, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

Epsilon-poly-l-lysine alleviates brown blotch disease of postharvest Agaricus bisporus mushrooms by directly inhibiting Pseudomonas tolaasii and inducing mushroom disease resistance - Rui Song; Xiuhong Wang; Lu Jiao; Hanyue Jiang; Shuai Yuan; Lei Zhang; Zixuan Shi; Zhenchuan Fan; Demei Meng (Pesticide Biochemistry and Physiology, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Modulating surface zinc species via facet engineering for efficient electroreduction of CO2 to CO - Junjie Wang; Zhaozhao Zhu; Yingxi Lin; Xueqiang Qi; Zhao Li; Jinxia Jiang; Xiaobin Niu; Jun Song Chen; Rui Wu (Chemical Engineering Journal, 2024)

Hollow-adjustable polymer microneedles for prolonged hypoglycemic effect on diabetic rats - Tianqi Liu; Yanfang Sun; Wenjing Zhang; Rui Wang; Xinyu Lv; Lei Nie; Amin Shavandi; Khaydar E. Yunusov; Guohua Jiang (Chemical Engineering Journal, 2024)

Constructing novel deep eutectic composites based on hydrogen bond network as anode material for lithium-ion batteries - Yiting Wang; Yifei Li; Jiali Chai; Qingmeng Li; Jiakai Du; Yichuan Rui; Bohejin Tang; Lei Jiang (Chemical Engineering Journal, 2024)

In situ bioprinting of double network anti-digestive xanthan gum derived hydrogel scaffolds for the treatment of enterocutaneous fistulas - Kang Chen; Jinjian Huang; Ze Li; Jinpeng Zhang; Sicheng Li; Canwen Chen; Ye Liu; Guiwen Qu; Yitian Teng; Rui Ma; Zongan Li; Yungang Jiang; et al. (Carbohydrate Polymers, 2024)

Investigating the Immunogenic Cell Death-Dependent Subtypes and Prognostic Signature of Triple-Negative Breast Cancer - Youyang Shi; Yuanyuan Wu; Feifei Li; Kexin Jiang; Xiaofang Fang; Yu Wang; Xiaoyun Song; Rui Wang; Lixin Chen; Jinzhou Zheng; Chunyu Wu; Yuenong Qin; et al. (Phenomics, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Spatiotemporal distribution, source analysis and ecological risk assessment of polychlorinated biphenyls (PCBs) in the Bohai Bay, China - Shan Jiang; Mengmeng Wan; Kun Lin; Yanshan Chen; Rui Wang; Liju Tan; Jiangtao Wang (Marine Pollution Bulletin, 2024)

Diterpenolignans and cephalotane diterpenoids from Cephalotaxus oliveri mast. with antitumor activity - Chunyu Jiang; Zimeng Han; Wen Sun; Jiayi Tan; Guiwen Gao; Xuan Wang; Huiming Hua; Rui Zhao; Tong Han (Phytochemistry, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

Meteoric diagenesis influenced by East Asian Summer Monsoon: A case study from the Pleistocene carbonate succession, Xisha Islands, South China Sea - Lü Wu; Rui Wang; Kefu Yu; Min Ren; Simone Booker; Ruoxia Shen; Wei Jiang; Shendong Xu; Tianlai Fan; Songye Wu; Qiushuang Qin; Xingchi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Performance analysis of the comprehensive energy system based on active energy storage-discharge technology under time-sharing electricity price operation strategy - Dong Zhang; Yuzhan Jiang; Shaohua Wang; Haoran Li; Jianhua Bai; Rui Zhang; Zhoujian An (Journal of Cleaner Production, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

Migration characteristics and local capillary trapping mechanism after the CO2 leakage out of saline aquifers - Guodong Cui; Zhe Hu; Yanyong Wang; Shu Jiang; Rui Wang (Fuel, 2024)

Tree-ring structured phase change materials with high through-plane thermal conductivity and flexibility for advanced thermal management - Wan-jun Jiang; Rui-qing Wang; Ting-yu Zhu; Mai Feng; De-xiang Sun; Jing-hui Yang; Xiao-dong Qi; Yong Wang (Chemical Engineering Journal, 2024)

The combination of nanotechnology and potassium: applications in agriculture - Qibin Wang; Chen Shan; Peng Zhang; Weichen Zhao; Guikai Zhu; Yi Sun; Quanlong Wang; Yaqi Jiang; Noman Shakoor; Yukui Rui (Environmental Science and Pollution Research, 2023)

Recent advances in the development of bitter gourd seed oil: from chemical composition to potential applications - Huiling Wang; Xiaoyan Shuai; Shuxin Ye; Rui Zhang; Muci Wu; Sijia Jiang; Yubao Li; Dong Wu; Jingren He (Critical Reviews in Food Science and Nutrition, 2023)

Longitudinal wastewater surveillance of four key pathogens during an unprecedented large-scale COVID-19 outbreak in China facilitated a novel strategy for addressing public health priorities–A proof of concept study - Songzhe Fu; Yixiang Zhang; Rui Wang; Zhiqiang Deng; Fenglan He; Xiaotong Jiang; Lixin Shen (Water Research, 2023)

Fabrication of high permeability and antifouling composite membrane loaded with Fe3O4 nanoparticles via a magnetic field induced phase separation - Meng Zhang; Shu Jiang; Xishou Guo; Xiaobin Tang; Langming Bai; Jinlong Wang; Han Zhang; Daliang Xu; Rui Wu; Luming Liu; Heng Liang (Journal of Water Process Engineering, 2023)

Volatile organic compounds of Bacillus spp. as an emerging antifungal resource play a significant role in fruit postharvest disease control - Lijun Ling; Yao Li; Kunling Jiang; Yuanyuan Wang; Hong Luo; Wenting Cheng; Mingmei Pang; Lijun Feng; Rui Yue; Yongpeng Zhou (Food Bioscience, 2023)

Characteristics of dissolved organic matter in point-source wastewaters at a petrochemical plant: Molecular constituents and contributions to the influent of wastewater treatment plant - Yue Kou; Baiyu Yang; Juntao Jiang; He Sun; Rui Zhang; Zhuoyu Li; Qinghong Wang; Quan Shi; Chunmao Chen (Environmental Research, 2023)

Single-cell transcriptome analysis revealing the intratumoral heterogeneity of ccRCC and validation of MT2A in pathogenesis - Jie Wang; Zili Zuo; Zongze Yu; Zhigui Chen; Xiangdi Meng; Zhaosen Ma; Jiqiang Niu; Rui Guo; Lisa Jia Tran; Jing Zhang; Tianxiao Jiang; Fangdie Ye; et al. (Functional & Integrative Genomics, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Natural ocean iron fertilization and climate variability over geological periods - Hai‐Bo Jiang; David A. Hutchins; Wentao Ma; Rui‐Feng Zhang; Mark Wells; Nianzhi Jiao; Yuntao Wang; Fei Chai (Global Change Biology, 2023)
Marine primary producers are largely dependent on and shape the Earth's climate, although their relationship with climate varies over space and time. The growth of phytoplankton and associated marine primary productivity in most of the modern global ocean is limited by the supply of nutrients, including the micronutrient iron. The addition of iron via episodic and frequent events drives the biological carbon pump and promotes the sequestration of atmospheric carbon dioxide (CO 2 ) into the ocean. However, the dependence between iron and marine primary producers adaptively changes over different geological periods due to the variation in global climate and environment. In this review, we examined the role and importance of iron in modulating marine primary production during some specific geological periods, that is, the Great Oxidation Event (GOE) during the Huronian glaciation, the Snowball Earth Event during the Cryogenian, the glacial–interglacial cycles during the Pleistocene, and the period from the last glacial maximum to the late Holocene. Only the change trend of iron bioavailability and climate in the glacial–interglacial cycles is consistent with the Iron Hypothesis. During the GOE and the Snowball Earth periods, although the bioavailability of iron in the ocean and the climate changed dramatically, the changing trend of many factors contradicted the Iron Hypothesis. By detangling the relationship among marine primary productivity, iron availability and oceanic environments in different geological periods, this review can offer some new insights for evaluating the impact of ocean iron fertilization on removing CO 2 from the atmosphere and regulating the climate.

Engineering a Pseudomonas putida as living quorum quencher for biofilm formation inhibition, benzenes degradation, and environmental risk evaluation - Yi-Mei Xue; Yong-Chao Wang; Yu-Ting Lin; Guan-Yu Jiang; Rui Chen; Ruo-Lin Qin; Xiao-Qiang Jia; Can Wang (Water Research, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Cleanable natural-sugar-alcohol-based polyester membrane for highly efficient molecular separation - Xiongwei Luo; Yue Wang; Yaoli Guo; Qieyuan Gao; Rui Zhao; Yanyan Liu; Riri Liu; Lei Jiang; Zhaohuan Mai; Hideto Matsuyama; Pengrui Jin (Resources, Conservation and Recycling, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

Assessing the potential risks, sources and the relationship between the dissolved and particulate polycyclic aromatic hydrocarbons (PAHs) in the typical semi-enclosed bay, Bohai Bay of China - Kun Lin; Rui Wang; Liju Tan; Shan Jiang; Hongyan Xu; Yali Cao; Jiangtao Wang (Marine Environmental Research, 2023)

Corrigendum to “Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits” [Eur. J. Agron. 150 (2023) 126955] - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Novel Fe trihalides solid molten salt-FeX3 (X = F, Cl, Br) via one-step method with low temperature as anodes of lithium-ion batteries - Yifei Li; Yiting Wang; Zhiyuan Chen; Qingmeng Li; Jiakai Du; Jiali Chai; Longzhen Wang; Yichuan Rui; Lei Jiang; Bohejin Tang (Chemical Engineering Journal, 2023)

Surface engineered long-lasting antibacterial Janus cotton fabrics with excellent moisture/thermal management properties - Lujie Wang; Maoshuang Chen; Rui Cai; Jingjing Jiang; Shuangfei Xiang; Xiangdong Liu; Hongyan Diao (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Comprehensive properties of non-penetrating and penetrating deep convection precipitation in summer over the Tibetan Plateau derived from GPM observations - Rui Wang; Zhongshan Jiang; Fengjiao Chen; Wenshou Tian; Liangliang Li; Hongying Tian; Jiali Luo (Atmospheric Research, 2023)

Linear relationship between CH4 fluxes and atmospheric CO2 concentration levels controlled by rice biomass and soil methanogenic communities - Yuanyuan Wang; Zhenghua Hu; Shuqi He; Qiang Jing; Lidong Shen; Chao Liu; Zhurong Wu; Wei Huang; Guihua Lu; Rui Cao; Kezhi Zheng; Ning Dong; et al. (Nutrient Cycling in Agroecosystems, 2023)

Coarse woody debris and litter layer exert differential roles in nursing soil fungal communities across a subalpine forest successional series - Zhihui Wang; Fei Li; Jianfeng Hou; Xuqing Li; Rui Cao; Yurui Jiang; Yuchen Lu; Shuning Ma; Wanqin Yang (Acta Oecologica, 2023)

Symbiotic hemolymph bacteria reduce hexavalent chromium to protect the host from chromium toxicity in Procambarus clarkii - Cheng-Ming Yin; Rui-Geng Niu; Hui Wang; Xian-Yao Li; Qi-Fan Zeng; Jiang-Feng Lan (Journal of Hazardous Materials, 2023)

Nano-agriculture and nitrogen cycling: Opportunities and challenges for sustainable farming - Quanlong Wang; Li Gao; Yuanbo Li; Noman Shakoor; Yi Sun; Yaqi Jiang; Guikai Zhu; Fayuan Wang; Yunze Shen; Yukui Rui; Peng Zhang (Journal of Cleaner Production, 2023)

Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

From anaerobic digestion to single cell protein synthesis: A promising route beyond biogas utilization - Rui Li; XiaoLei Fan; YuFeng Jiang; RuoNan Wang; RongBo Guo; Yifeng Zhang; ShanFei Fu (Water Research, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Properties of dolomitizing fluids indicated by rare earth elements: A case study of the Upper Miocene to Pliocene dolostone on the Xisha Islands, South China Sea - Ruoxia Shen; Anjiang Shen; Kefu Yu; Cole A. McCormick; Wei Jiang; Yang Xiao; Lü Wu; Rui Wang (Sedimentary Geology, 2023)

A mega study of antibiotics contamination in Eastern aquatic ecosystems of China: occurrence, interphase transfer processes, ecotoxicological risks, and source modeling - Abdul Qadeer; Guo Rui; Liu Yaqing; Dai Ran; Chengyou Liu; Dong Jing; Muhammad Anis; Mengyang Liu; Shuhang Wang; Xia Jiang; Xingru Zhao (Journal of Hazardous Materials, 2023)

Structure, rheology, and antifreeze property of the exopolysaccharide from Naematelia aurantialba through basidiospore fermentation - Tao Sun; Xiaoyi Xu; Yuhang Ma; Hao jiang; Kai Yang; Rui Wang; Yian Gu; Sha Li; Yibin Qiu; Dafeng Sun; Hong Xu; Peng Lei (Food Hydrocolloids, 2023)

Tailoring zincophilicity via amorphous Se-rich selenides coating for stable Zn anode - Guoquan Jiang; Rui Xue; Linxin He; Junchao Zhu; Nan Qiu; Yuan Wang (Chemical Engineering Journal, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Remarkable bioactivity, bio-tribological, antibacterial, and anti-corrosion properties in a Ti-6Al-4V-xCu alloy by laser powder bed fusion for superior biomedical implant applications - Jiang Ju; Rui Zan; Zhao Shen; Chenchen Wang; Peng Peng; Jun Wang; Baode Sun; Bo Xiao; Qian Li; Shaofei Liu; Tao Yang (Chemical Engineering Journal, 2023)

pCtFSG2, a flower-specific promoter with suitable promoter activity in safflower - Jiang Chen; Chaoxiang Ren; Jie Wang; Bin Xian; Rui Wang; Qinghua Wu; Jin Pei (Journal of Plant Biochemistry and Biotechnology, 2023)

Transient analyses for China initiative Accelerator Driven System using the extended BELLA code - Guan Wang; Janne Wallenius; Rui Yu; Wei Jiang; Lu Zhang; Xin Sheng; Di Yun; Long Gu (Annals of Nuclear Energy, 2023)

Insights into the quantitative structure–activity relationship for ionic liquids: a bibliometric mapping analysis - Rui Huang; Hui Liu; Ze Wei; Yi Jiang; Kai Pan; Xin Wang; Jie Kong (Environmental Science and Pollution Research, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Decorative ZIF-8 covered facet-dependent Cu2O toward highly efficient adsorption by reduction U(VI) to U(IV) - Xiaomei Zhang; Nina Yan; Min Wang; Xizhi Jiang; Rui Xu; Min Feng; Lei Xu; Shaochun Tang (Journal of Environmental Chemical Engineering, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

Assessing the occurrence and sources of synthetic additive pollutants in lake sediments using fecal and sewage markers - Rui Du; Xiaoxia Feng; Pu Wang; Ruiqiang Yang; Gang Li; Jianjie Fu; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

High prevalence of vitamin D deficiency in Asia: A systematic review and meta-analysis - Zhiwei Jiang; Rui Pu; Na Li; Chaozhen Chen; Jialu Li; Wei Dai; Yuchen Wang; Jinxing Hu; Danji Zhu; Qiong Yu; Yuan Shi; Guoli Yang (Critical Reviews in Food Science and Nutrition, 2023)

A method establishment and application for biofilm quorum quenching activity assay - Zhen Tong; Yong-Chao Wang; Guan-Yu Jiang; Xu-Rui Hu; Yi-Mei Xue; Can Wang (Chemosphere, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Characteristics, sources and health risks of organotin compounds in marine organisms from the seas adjacent to the eastern ports of China - Sheng-Nan Shu; Rui-Tong Jiang; Jie Yin; Qian Wang; Lei Su; Nicholas J. Craig; Juan-Ying Li (Regional Studies in Marine Science, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Novel insights into tumorigenesis and prognosis of endometrial cancer through systematic investigation and validation on mitophagy-related signature - Rui Sun; Xiaoyu Zhou; Tong Wang; Yao Liu; Lina Wei; Ziyi Qiu; Chunping Qiu; Jie Jiang (Human Cell, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

Lipoxin A4 methyl ester attenuated ketamine-induced neurotoxicity in SH-SY5Y cells via regulating leptin pathway - Rui Zhang; Xueji Wang; Ziyu Xie; Tianyu Cao; Sufang Jiang; Lining Huang (Toxicology in Vitro, 2023)

Research progress of volatile organic compounds produced by plant endophytic bacteria in control of postharvest diseases of fruits and vegetables - Lijun Ling; Yuanyuan Wang; Wenting Cheng; Kunling Jiang; Hong Luo; Mingmei Pang; Rui Yue (World Journal of Microbiology and Biotechnology, 2023)

Correction to: Inhibition of mGluR5 alters BDNF/TrkB and GLT‑1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD‑like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Hippocampus: Molecular, Cellular, and Circuit Features in Anxiety - Hu-Jiang Shi; Shuang Wang; Xin-Ping Wang; Rui-Xin Zhang; Li-Juan Zhu (Neuroscience Bulletin, 2023)

Correction: Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Measuring static and dynamic industrial eco-efficiency in China based on the MinDS–Malmquist–Luenberger model - Pei-Pei Jiang; Yuan Wang; Jin Luo; Lin Zhu; Rui Shi; Song Hu; Xiaodong Zhu (Environment, Development and Sustainability, 2023)

Examining moisture contribution for precipitation in response to climate change and anthropogenic factors in Hengduan Mountain Region, China - Xingxing Zhang; Zhaofei Liu; Yubo Liu; Liguang Jiang; Rui wang; Hou Jiang; Jing Li; Qiuhong Tang; Zhijun Yao (Journal of Hydrology, 2023)

Abiotic transformation of synthetic progestins in representative soil mineral suspensions - Xingjian Yang; Rui Wang; Zhili He; Xiong Dai; Xiuping Jiang; He Liu; Yongtao Li (Journal of Environmental Sciences, 2023)

Heavy metals in riverine/estuarine sediments from an aquaculture wetland in metropolitan areas, China: Characterization, bioavailability and probabilistic ecological risk - Hai-Song Li; Yang-Guang Gu; Rui-Ze Liang; Ya-Su Wang; Richard W. Jordan; Liang-Gen Wang; Shi-Jun Jiang (Environmental Pollution, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Crushing combined with high–frequency turning can promote material degradation of sheep manure compost on the Qinghai–Tibet Plateau by improving the microbial metabolic function - Rui Cai; Xinyu Cui; Xiaohui Cao; Xin Jiang; Rongze Wang; Chuncheng Xu (Journal of Environmental Chemical Engineering, 2023)

Large-scale mapping of solifluction terraces in the southeastern Tibetan Plateau using high-resolution satellite images and deep learning - Ronggang Huang; Liming Jiang; Zhida Xu; Rui Guo; Fujun Niu; Hansheng Wang (Geomorphology, 2023)

Apatite and fluorite control the transport of tungsten in calcium-bearing hydrothermal fluids - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Zi-Qi Jiang; Lin-Bo Shang; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Inhibition of mGluR5 alters BDNF/TrkB and GLT-1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD-like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Highly efficient aerobic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid over halloysite nanotubes-templated nitrogen-doped carbon supported bimetallic AuPd catalyst - Fang Wang; Changhao Yan; Rui Jiang; Yao Chen; Yanan Wei; Yu Cao; Wen Guan; Pengwei Huo; Yunlei Zhang (Applied Clay Science, 2023)

Morphological alterations in C57BL/6 mouse intestinal organoids as a tool for predicting chemical-induced toxicity - Ziwei Wang; Shen Chen; Yaqin Pang; Lizhu Ye; Qi Zhang; Xinhang Jiang; Rui Zhang; Miao Li; Zhanyu Guo; Yue Jiang; Daochuan Li; Xiumei Xing; et al. (Archives of Toxicology, 2023)

Diffusion simulation and risk assessment model establishment of chlorine gas leakage based on terrain conditions - Xiao-ting Ren; Xiao-ling Ma; Jiang-zheng Liu; Rui Liu; Chen-qian Zhao; Hao Wu; Zhao Wang; Chun-xu Hai; Xiao-di Zhang (Environmental Science and Pollution Research, 2023)

Flow regime changes in the Lancang River, revealed by integrated modeling with multiple Earth observation datasets - Xingxing Zhang; Liguang Jiang; Zhaofei Liu; Cecile M.M. Kittel; Zhijun Yao; Daniel Druce; Rui Wang; Christian Tøttrup; Jun Liu; Hou Jiang; Peter Bauer-Gottwein (Science of The Total Environment, 2023)

Corrigendum to “A review of salt precipitation during CO2 injection into saline aquifers and its potential impact on carbon sequestration projects in China” [Fuel 334 (2022) 126615] - Guodong Cui; Zhe Hu; Fulong Ning; Shu Jiang; Rui Wang (Fuel, 2023)

Detecting ionizing radiation dose using composite hydrogel-based sensors - Li Jiang; Chengfang Zhang; Xinyue Xu; Rui Hu; Ping Zhang; Rensheng Wang; Xinjian Chen; Liang Hu (Chemical Engineering Journal, 2023)

Silencing P25, HC-Pro and Brp1 of Potato Virus (Viroid) Using Artificial microRNA Confers Resistance to PVX, PVY and PSTVd in Transgenic Potato - Lili Jiang; Rui Mu; Ziquan Wang; Shangwu Liu; Dianqiu Lu (Potato Research, 2023)

Antimicrobial peptide CB-M exhibits direct antifungal activity against Botrytis cinerea and induces disease resistance to gray mold in cherry tomato fruit - Xiaomin Yang; Yating Wang; Hanyue Jiang; Rui Song; Yongguo Liu; Honglian Guo; Demei Meng (Postharvest Biology and Technology, 2023)

Interactions of organic phosphorus with soil minerals and the associated environmental impacts: A review - Yupeng YAN; Biao WAN; Rui JIANG; Xiaoming WANG; Hui WANG; Shuai LAN; Qin ZHANG; Xionghan FENG (Pedosphere, 2023)

Self-assembly of Au nanocrystals into large-area 3-D ordered flexible superlattice nanostructures arrays for ultrasensitive trace multi-hazard detection - Wei Liu; Qian Li; Jiabin Wu; Weizhe Wang; Rui Jiang; Chunli Zhou; Shuangbao Wang; Xueming Zhang; Tangyou Sun; Zhimou Xu; Dingsheng Wang (Journal of Hazardous Materials, 2023)

Accurate combination forecasting of wave energy based on multiobjective optimization and fuzzy information granulation - Yuqi Dong; Jianzhou Wang; Rui Wang; He Jiang (Journal of Cleaner Production, 2023)

A review of salt precipitation during CO2 injection into saline aquifers and its potential impact on carbon sequestration projects in China - Guodong Cui; Zhe Hu; Fulong Ning; Shu Jiang; Rui Wang (Fuel, 2023)

Experimental and kinetic study on JP-10/air autoignition and the effect of NO2 at high temperatures - Lei Shi; Ping Xu; Rui Wang; Weixin Tang; Tao Ding; Rongpei Jiang; Changhua Zhang (Fuel, 2023)

Molecular characterization and immune functions of lipasin in Nile tilapia (Oreochromis niloticus): Involvement in the regulation of tumor necrosis factor-α secretion - Rui Dong; Zixi Wang; Qianqian Zhao; Yisha Yan; Quan Jiang (Fish & Shellfish Immunology, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Seasonal variation and ecological risk assessment of Pharmaceuticals and Personal Care Products (PPCPs) in a typical semi-enclosed bay — The Bohai Bay in northern China - Kun Lin; Rui Wang; Tongzhu Han; Liju Tan; Xue Yang; Mengmeng Wan; Yanshan Chen; Ting Zhao; Shan Jiang; Jiangtao Wang (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Hotspots of riverine greenhouse gas (CH4, CO2, N2O) emissions from Qinghai Lake Basin on the northeast Tibetan Plateau - Penglin Lin; Zhiheng Du; Lei Wang; Jingfeng Liu; Qian Xu; Jia Du; Rui Jiang (Science of The Total Environment, 2023)

Analytical solutions on non-Darcy seepage of grouted and lined subsea tunnels under dynamic water levels - Xiang Liu; Dongchi Wang; Yu Zhang; Annan Jiang; Qian Fang; Rui Zhang (Ocean Engineering, 2023)

A stack-up electrochemical device based on metal-organic framework modified carbon paper for ultra-trace lead and cadmium ions detection - Yue-Hong Pang; Qiu-Yu Yang; Rui Jiang; Yi-Ying Wang; Xiao-Fang Shen (Food Chemistry, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Leakage Fault Diagnosis of Lifting and Lowering Hydraulic System of Wing-Assisted Ships Based on WPT-SVM - Ranqi Ma; Haoyang Zhao; Kai Wang; Rui Zhang; Yu Hua; Baoshen Jiang; Feng Tian; Zhang Ruan; Hao Wang; Lianzhong Huang (Journal of Marine Science and Engineering, 2022)
Wing-assisted technology is an effective way to reduce emissions and promote the decarbonization of the shipping industry. The lifting and lowering of wing-sail is usually driven by hydraulic system. Leakage, as an important failure form, directly affects the safety as well as the functioning of hydraulic system. To increase the system reliability and improve the wing-assisted effect, it is essential to conduct leakage fault diagnosis of lifting and lowering hydraulic system. In this paper, an AMESim simulation model of lifting and lowering hydraulic system of a Very Large Crude Carrier (VLCC) is established to analyze the operation characteristics of the hydraulic system. The effectiveness of the model is verified by the operation data of the actual hydraulic system. On this basis, a wavelet packet transform (WPT)-based sensitive feature extracting method of leakage fault for the hydraulic system is proposed. Subsequently, a support vector machine (SVM)-based multi-classification model and diagnosis method of leakage fault are proposed. The study results show that the proposed method has an accuracy of as high as 97.5% for six leakage fault modes. It is of great significance for ensuring the reliability of the wing-sail operation and improving the utilization rate of the offshore wind resources.

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

A novel therapeutic strategy for atherosclerosis: autophagy-dependent cholesterol efflux - Haipeng Guo; Dongmei Wei; Rui Liu; Chao Zhang; Song Jiang; Weijia Wang; Hongzhe Hu; Lijuan Shen; Xiaofei Liang (Journal of Physiology and Biochemistry, 2022)

Effects of the soaking-related parameters in a combined freezing-based seawater desalination process - Hui Yang; Yuanfei Jiang; Rui Wang; Bingyan Dong; Mengxiao Fu (Environmental Science and Pollution Research, 2022)

Trophic Niche Partitioning of Five Sciaenidae Species Sampled in Zhoushan Archipelago Waters via Stable Isotope Analysis - Jing Wang; Ri-Jin Jiang; Yi Xiao; Rui Yin; Feng Chen; Yong-dong Zhou; Han-Xiang Xu (Frontiers in Marine Science, 2022)
Sciaenid fishes are usually associated with large freshwater inputs and are the most important economic fish on the coastal shelf off mainland China. To compare the differences in ecological niche and resource sharing among different populations of Sciaenidae species, we collected samples of Larimichthys polyactis , Collichthys lucidus , Johnius belangerii , Nibea albiflora , and Miichthys miiuy from Zhoushan Archipelago waters from 2019 to 2021 and investigated the carbon and nitrogen isotopic values in muscle tissues, the contribution of each food resource, and trophic niche widths and overlaps. Significant differences were observed in both isotopes in the muscles of the five Sciaenid species. Zooplankton was a key food resource for all Sciaenid species. In addition to zooplankton, J. belangerii , N. albiflora , and M. miiuy also fed on benthos organisms. C. lucidus presented a wide trophic niche width and had extensive habitat use. The trophic niche occupied by N. albiflora and M. miiuy was narrow; they presented a high trophic level, with a high degree of trophic niche overlap. This study showed that sciaenid fishes have overlapping trophic niches due to their common feeding on zooplankton, and differences in body size, migration, habitat, and feeding choices led to the reasonable sharing of resources among the five sciaenid fishes, allowing the coexistence of these species.

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Erratum to: Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2022)

Establishment and optimization of PEG-mediated protoplast transformation in the microalga Haematococcus pluvialis - Chunli Guo; Muhammad Anwar; Rui Mei; Xinyi Li; Di Zhao; Yanan Jiang; Jieyi Zhuang; Chen Liu; Chaogang Wang; Zhangli Hu (Journal of Applied Phycology, 2022)
Genetic manipulation of Haematococcus pluvialis is difficult because of the lack of a stable and convenient transformation system. The pH124-EGFP-Ble vector containing ble as a selective gene and EGFP as a reporter gene was constructed and employed for effective transformation. H. pluvialis protoplasts were obtained by treating with cellulase and macerozeme. Then polyethylene glycol-mediated transformation was established by incubating the protoplast with the vector. To improve the transformation efficiency of H. pluvialis protoplasts, the transformation system was optimized in consideration of different influencing factors, including zeomycin concentration, growth stage, amount of transformed vector, linearization of the vector, and duration of low-intensity illumination. The integration and expression of ble and EGFP was confirmed in the transformants. Moreover, the optimal combination for protoplast transformation of H. pluvialis was determined to be 5 µg of the linearized vector used to transform cells in the log growth phase, and then the transformed protoplasts allowed to recover under low-intensity illumination for 6 h. This study represents and describes the successful development of an H. pluvialis transformation protocol using protoplasts, which will enable convenient genetic manipulation of this important algal species.

Analyzing the mechanism of nitrous oxide production in aerobic phase of anoxic/aerobic sequential batch reactor from the perspective of key enzymes - Rui Yang; Lin-jiang Yuan; Ru Wang; Zhi-xian He; Lin Lei; Yan-chen Ma (Environmental Science and Pollution Research, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Positron Emission Tomography Molecular Imaging for Phenotyping and Management of Lymphoma - Xiaohui Zhang; Han Jiang; Shuang Wu; Jing Wang; Rui Zhou; Xuexin He; Shufang Qian; Shuilin Zhao; Hong Zhang; Ali Cahid Civelek; Mei Tian (Phenomics, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Microseismic Monitoring of Rock Mass Fracture Response to Blasting Excavation of Large Underground Caverns Under High Geostress - Jin-Shuai Zhao; Bing-Rui Chen; Quan Jiang; Jian-Fei Lu; Xian-Jie Hao; Shu-Feng Pei; Fei Wang (Rock Mechanics and Rock Engineering, 2022)

Correction to: A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Serine protease HtrA2/Omi regulates adaptive mitochondrial reprogramming in the brain cortex after ischemia/reperfusion injury via UCP2-SIRT3-PGC1 axis - Hao Meng; Lian-Kun Sun; Jing Su; Wan-Yu Yan; Yao Jin; Xin Luo; Xian-Rui Jiang; Hong-Lei Wang (Human Cell, 2022)

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Knockdown of lncRNA LUCAT1 attenuates sepsis‑induced myocardial cell injury by sponging miR-642a - Jing Wang; Shaobin Xin; Rui Yang; Jiawei Jiang; Youjie Qiao (Mammalian Genome, 2021)

Cognition effectiveness of continuous positive airway pressure treatment in obstructive sleep apnea syndrome patients with cognitive impairment: a meta-analysis - Xinzhao Jiang; Zicong Wang; Nan Hu; Ying Yang; Rui Xiong; Zhengqi Fu (Experimental Brain Research, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2021)

Insight into the Interaction Between Microplastics and Microorganisms Based on a Bibliometric and Visualized Analysis - Yanping Jiang; Wanjun Xia; Rui Zhao; Mengge Wang; Jinfeng Tang; Yongjun Wei (Bulletin of Environmental Contamination and Toxicology, 2021)

A high-resolution timescale for the Miocene Shanwang diatomaceous shale lagerstätte (China): development of Wavelet Scale Series Analysis for cyclostratigraphy - Jifeng Yu; Xinlong Pang; Wenzhao Fu; Jason Hilton; Mingmei Liang; Zongkai Jiang; Xiuli Zhao; Wenyan Qiao; Suo Shi; Diandong Zhang; Huitao Cao; Haibo Jia; et al. (Geosciences Journal, 2021)

Glycomyces salinus sp. nov., an actinomycete isolated from a hypersaline habitat - Rui Li; Gang-Qiang Jiang; Yun Wang; Yi-Guang Chen; En-Min Zhou; Shu-Kun Tang (Archives of Microbiology, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Insights into heat response mechanisms in Clematis species: physiological analysis, expression profiles and function verification - Hao Zhang; Changhua Jiang; Rui Wang; Long Zhang; Ruonan Gai; Siyuan Peng; Yi Zhang; Chanjuan Mao; Yuxia Lou; Jianbin Mo; Shucheng Feng; Feng Ming (Plant Molecular Biology, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Screening and Analysis of Multiclass Veterinary Drug Residues in Animal Source Foods using UPLC-Q-Exactive Orbitrap/MS - Wentao Zhao; Rui Jiang; Wenping Guo; Chao Guo; Shilei Li; Juanqiang Wang; Shouwei Wang; Yingying Li (Bulletin of Environmental Contamination and Toxicology, 2021)
A rapid, simple, and sensitive method of detecting veterinary drug residues in animal food sources, including poultry and pork, was developed and validated. The method was optimized for over 155 veterinary drugs of 21 different classes. Sample pretreatment included a simple solid-liquid extraction step with 0.2% formic acid-acetonitrile-water and a purification step with a PRiME HLB (hydrophile-lipophile balance) solid-phase extraction cartridge. Data were collected using ultra-high-performance liquid chromatography coupled to Quadrupole-Exactive Orbitrap mass spectrometry. The limits of detection of 155 veterinary drugs ranged from 0.1 µg/kg to 10 µg/kg. The recovery rates were between 79.2 and 118.5 % in all matrices studied, with relative standard deviation values less than 15% (n = 6). The evaluated method allows the reliable screening, quantification, and identification of 155 veterinary drug residues in animal source food and has been successfully applied in authentic samples.

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2021)

Abiotic and biotic controls of soil dissolved organic nitrogen along a precipitation gradient on the Tibetan plateau - Lili Jiang; Shiping Wang; Zhe Pang; Changshun Wang; Fandong Meng; Zhichun Lan; Xiaoqi Zhou; Yaoming Li; Zhenhua Zhang; Caiyun Luo; Davey L. Jones; Yichao Rui; et al. (Plant and Soil, 2021)

Combining forecast of landslide displacement based on chaos theory - Xunchang Li; Chao Jiang; Rui Xu; Wei Yang; HaoHao Wang; Yu Zou (Arabian Journal of Geosciences, 2021)

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Non-thermal plasma-enhanced low-temperature catalytic desulfurization of electrolytic aluminum flue gas by CuO-ZrSnO4: experimental and numerical analysis - Zhiyuan Ning; Lianshuang Jiang; Zeyue Wang; Rui Huang; Zhenyu Zhang; Qiulin Zhang; Ping Ning (Environmental Science and Pollution Research, 2020)

Genome-wide identification of microRNAs and phased siRNAs in soybean roots under long-term salt stress - Qian Wang; Yingxia Yang; Guoqing Lu; Xianjun Sun; Youren Feng; Shuangyong Yan; Huiyuan Zhang; Qiyan Jiang; Hui Zhang; Zheng Hu; Rui Chen (Genes & Genomics, 2020)

Development of SNP markers for the bighead carp (Hypophthalmichthys nobilis) by using transcriptomic sequences - Rui An; Jianjun Fu; Bingjie Jiang; Wenbin Zhu; Lanmei Wang; Mingkun Luo; Zaijie Dong (Conservation Genetics Resources, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Modeling the ecosystem response of the semi-closed Daya Bay to the thermal discharge from two nearby nuclear power plants - Rui Jiang; You-Shao Wang (Ecotoxicology, 2020)

Transcriptional regulation of microRNA-126a by farnesoid X receptor in vitro and in vivo - Yi Yan; Shichao Wang; Rui Wang; Puxuan Jiang; Yaqing Chen; Liang Zhang; Chenjiao Hou; Lisheng Zhang (Biotechnology Letters, 2020)

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

miR-140-3p aggregates osteoporosis by targeting PTEN and activating PTEN/PI3K/AKT signaling pathway - Ruofeng Yin; Jiajia Jiang; Huimin Deng; Zhaobin Wang; Rui Gu; Fei Wang (Human Cell, 2020)

Experimental and numerical study on the load and deformation mechanism of a flexible net barrier under debris flow impact - Rui Jiang; Wen-ping Fei; Hong-wei Zhou; Miao Huo; Jia-wen Zhou; Jia-mei Wang; Jia-jun Wu (Bulletin of Engineering Geology and the Environment, 2020)

Drought characteristics and its impact on changes in surface vegetation from 1981 to 2015 in the Yangtze River Basin, China - Weixia Jiang; Lunche Wang; Lan Feng; Ming Zhang; Rui Yao (International Journal of Climatology, 2020)
Located in the subtropical monsoon climate area of China, the Yangtze River Basin (YRB) had been frequently affected by drought events recently. Based on standardized precipitation evapotranspiration Index (SPEI) and enhanced vegetation index (EVI), the characteristics of drought in the YRB and the influence of drought on vegetation in different seasons were investigated by maximum correlation ( R max ) between 1981 and 2015. The results showed that: (a) Droughts occurred frequently but had no obvious regularity in the YRB from 1981 to 2015. The drought intensity in autumn and winter were slightly higher than that in spring and summer. The autumn droughts in Sichuan Basin were the most serious, followed by the spring droughts in the middle and lower reaches of the YRB; (b) Annual SPEI series at 102 stations exhibited a downward trend and 72 stations exhibited an upward trend. There was no station showing a significant downward trend and two stations showing a significant upward trend. There was a drying trend in autumn and winter, and a wetting trend in spring and summer. The eastern area of the YRB shows a more arid trend in spring and autumn, as well as in the southwest in winter; (c) 90% of YRB showed a significant positive correlation ( p

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Community structure of Anaeromyxobacter in Fe(III) reducing enriched cultures of paddy soils - Kun Wang; Rong Jia; Lina Li; Rui Jiang; Dong Qu (Journal of Soils and Sediments, 2020)

Heritability of resistance-related gene expression traits and their correlation with body size of clam Meretrix petechialis - Fengjuan Jiang; Xin Yue; Shujing Zhang; Jiajia Yu; Rui Wang; Baozhong Liu; Hongxia Wang (Journal of Oceanology and Limnology, 2020)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Mercury exposure in sedentary and migratory Charadrius plovers distributed widely across China - Tongping Su; Xin Lin; Qin Huang; Demeng Jiang; Chi Zhang; Xuecong Zhang; Caroline Dingle; Eben Goodale; Pinjia Que; Rui Wang; Yang Liu (Environmental Science and Pollution Research, 2020)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Model test on failure and control mechanism of surrounding rocks in tunnels with super large sections - Rui Pan; Qi Wang; Bei Jiang; Shucai Li (Arabian Journal of Geosciences, 2019)

Two new sesquineolignans from the seeds of Crataegus pinnatifida and their β -amyloid aggregation inhibitory activitiy - Rui Guo; Le Zhou; Peng Zhao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Aspergilolide, a steroid lactone produced by an endophytic fungus Aspergillus sp . MBL1612 isolated from Paeonia ostii - Pei-Liang Zhang; Gang Wang; Feng-Qing Xu; Jin-Song Liu; Ju-Tao Wang; Rui Zhang; Hai-Tao Liu; Jiang-Miao Hu; Guo-Kai Wang; Pei-Yun Wu (Natural Product Research, 2019)

A new coumarin from Juglans mandshurica Maxim induce apoptosis in hepatocarcinoma cells - Li-Li Lou; Peng Zhao; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Mechanical Effect Analysis and Comparative Site Tests on Surrounding Rock with Different Bolt Anchoring Lengths and Pre-tightening Forces - Qi Wang; Hongtao Wang; Rui Pan; Shucai Li; Manchao He; Bei Jiang; Qian Qin; Chong Zhang; Yingdong Xu (Geotechnical and Geological Engineering, 2019)

Depositional and diagenetic controls on the reservoir quality of Upper Triassic Chang-7 tight oil sandstones, southwestern Ordos basin, China - Ai Wang; Dakang Zhong; Haihua Zhu; Lele Guo; Zhuopei Li; Yangjinfeng Jiang; Xueqi Yang; Rui Xie; Xiaowei Zheng (Geosciences Journal, 2019)

Differential response to warming of the uptake of nitrogen by plant species in non-degraded and degraded alpine grasslands - Zhe Pang; Lili Jiang; Shiping Wang; Xingliang Xu; Yichao Rui; Zhenhua Zhang; Caiyun Luo; Yanfen Wang (Journal of Soils and Sediments, 2019)

Comparison of levofloxacin-based prophylaxis regimens for transrectal prostate biopsy: a prospective randomized single-center study - Rui Su; Kai-yun Wang; Dong Zhang; Ze-jun Yan; Jun-hui Jiang; Qi Ma (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Study on Surrounding Rock Stability of Small Clear-Distance Twin Highway Tunnel with Eight Lanes - Qing Jiang; Shu-guang Song; Tao Li; Kang Wang; Rui-hai Gu (Geotechnical and Geological Engineering, 2019)

Diagentic features of illite in Upper Triassic Chang-7 tight oil sandstones, Ordos Basin - Ai Wang; Dakang Zhong; Haihua Zhu; Lele Guo; Yangjinfeng Jiang; Xueqi Yang; Rui Xie (Geosciences Journal, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Plant organic N uptake maintains species dominance under long-term warming - Lili Jiang; Shiping Wang; Pang Zhe; Xingliang Xu; Paul Kardol; Yaoming Li; Lirong Zhang; Yanfen Wang; Zhong Lei; Zhichun Lan; Paul W. Hill; Zhenhua Zhang; et al. (Plant and Soil, 2018)

Comparative study on mitogenomes of green tide algae - Chuner Cai; Feng Liu; Ting Jiang; Lingke Wang; Rui Jia; Lingjie Zhou; Kai Gu; Jianfeng Ren; Peimin He (Genetica, 2018)

Complete nucleotide sequence of a novel monopartite begomovirus infecting Ageratum conyzoides in China - Pengbai Li; Chenchen Jing; Rui Wang; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Archives of Virology, 2018)

The role of autophagy in pulmonary hypertension: a double-edge sword - Rui Chen; Meiping Jiang; Bo Li; Wei Zhong; Zhongqun Wang; Wei Yuan; Jinchuan Yan (Apoptosis, 2018)

Alzheimer’s Disease Risk Variant rs2373115 Regulates GAB2 and NARS2 Expression in Human Brain Tissues - Guiyou Liu; Tao Wang; Rui Tian; Yang Hu; Zhifa Han; Pingping Wang; Wenyang Zhou; Peng Ren; Jian Zong; Shuilin Jin; Qinghua Jiang (Journal of Molecular Neuroscience, 2018)

Anemia and Iron Status Among Different Body Size Phenotypes in Chinese Adult Population: a Nation-Wide, Health and Nutrition Survey - Jiang Li; Cheng Xiao; Hui Yang; Yun Zhou; Rui Wang; Yongtong Cao (Biological Trace Element Research, 2018)

Three-dimensional numerical modeling of gravity anomalies based on Poisson equation in space-wavenumber mixed domain - Shi-Kun Dai; Dong-Dong Zhao; Qian-Jiang Zhang; Kun Li; Qing-Rui Chen; Xu-Long Wang (Applied Geophysics, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Association analysis between spatiotemporal variation of vegetation greenness and precipitation/temperature in the Yangtze River Basin (China) - Lifang Cui; Lunche Wang; Ramesh P. Singh; Zhongping Lai; Liangliang Jiang; Rui Yao (Environmental Science and Pollution Research, 2018)

Dietary exposure to cadmium of Shenzhen adult residents from a total diet study - Zhou Wang; Liubo Pan; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Ying Xiao; Weibin Bai; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

U–Pb zircon, geochemical and Sr–Nd–Hf isotopic constraints on age and origin of the intrusions from Wunugetushan porphyry deposit, Northeast China: implication for Triassic–Jurassic Cu–Mo mineralization in Mongolia–Erguna metallogenic belt - Kui-Feng Mi; Zhen-Jiang Liu; Rui-Bin Liu; Chun-Feng Li; Jian-Ping Wang; Run-Min Peng (International Geology Review, 2018)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Detection and phylogenetic analysis of Mycoplasma hyopneumoniae from Tibetan pigs in western China - Gang Qiu; Yapei Rui; Kun Li; Shucheng Huang; Zhaoqing Han; Xiaoqiang Wang; Wenteng Jiang; Houqiang Luo; Yanfang Lan; Jiakui Li (Tropical Animal Health and Production, 2017)

Limit Analysis of Roof Falling in Roadway with Water-Rich Surrounding Rock - Bei Jiang; Qi Wang; Li Gao; Shucai Li; Chong Zhang; Hongke Gao; Rui Pan (Geotechnical and Geological Engineering, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Identification and characterization of Orf virus 050 protein proteolysis - Han Wang; Junyi Jiang; Rui Ding; Xiaoping Wang; Meiying Liao; Jing Shao; Xiaohong Luo; Shuhong Luo; Chaohui Duan (Virus Genes, 2017)

Warming Effects on Ecosystem Carbon Fluxes Are Modulated by Plant Functional Types - Ji Chen; Yiqi Luo; Jianyang Xia; Kevin R. Wilcox; Junji Cao; Xuhui Zhou; Lifen Jiang; Shuli Niu; Katerina Y. Estera; Rujin Huang; Feng Wu; Tafeng Hu; et al. (Ecosystems, 2017)

Performance analysis and design of the optimal frequency-assisted phase tracking loop - Rui Jiang; Kedong Wang; Jinling Wang (GPS Solutions, 2017)

Performance analysis of a Kalman filter carrier phase tracking loop - Rui Jiang; Kedong Wang; Shihan Liu; Yong Li (GPS Solutions, 2017)

Molecular cloning and expression analysis of two FAD2 genes from chia (Salvia hispanica) - Yufei Xue; Nengwen Yin; Baojun Chen; Feifei Liao; Aung Naing Win; Jiayi Jiang; Rui Wang; Xiaoyun Jin; Na Lin; Yourong Chai (Acta Physiologiae Plantarum, 2017)

Cloning and expression of Perilla frutescens FAD2 gene and polymorphism analysis among cultivars - Yufei Xue; Xingcui Zhang; Rui Wang; Baojun Chen; Jiayi Jiang; Aung Naing Win; Yourong Chai (Acta Physiologiae Plantarum, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

Dietary Zinc Oxide Modulates Antioxidant Capacity, Small Intestine Development, and Jejunal Gene Expression in Weaned Piglets - Cui Zhu; Hang Lv; Zhuang Chen; Li Wang; Xiuju Wu; Zhongjian Chen; Weina Zhang; Rui Liang; Zongyong Jiang (Biological Trace Element Research, 2017)

Brain structure–function associations identified in large-scale neuroimaging data - Zhi Yang; Jiang Qiu; Peipei Wang; Rui Liu; Xi-Nian Zuo (Brain Structure and Function, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Dust aerosol properties and radiative forcing observed in spring during 2001–2014 over urban Beijing, China - Xingna Yu; Rui Lü; K. Raghavendra Kumar; Jia Ma; Qiuju Zhang; Yilun Jiang; Na Kang; Suying Yang; Jing Wang; Mei Li (Environmental Science and Pollution Research, 2016)

Dietary exposure to lead of adults in Shenzhen city, China - Liubo Pan; Zhou Wang; Zhaoqiong Peng; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Nimal Pathiraja; Ying Xiao; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Grazing modifies inorganic and organic nitrogen uptake by coexisting plant species in alpine grassland - Lili Jiang; Shiping Wang; Zhe Pang; Changshun Wang; Paul Kardol; Xiaoqi Zhou; Yichao Rui; Zhi chun Lan; Yanfen Wang; Xingliang Xu (Biology and Fertility of Soils, 2016)

Impact of climate change on regional irrigation water demand in Baojixia irrigation district of China - Xiao-jun Wang; Jian-yun Zhang; Mahtab Ali; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Zhuo Jiang (Mitigation and Adaptation Strategies for Global Change, 2016)

Kupffer-cell-expressed transmembrane TNF-α is a major contributor to lipopolysaccharide and D-galactosamine-induced liver injury - Peng Yang; Wenjing Zhou; Chenxi Li; Meng Zhang; Yaping Jiang; Rui Jiang; Hongping Ba; Cheng Li; Jing Wang; Bingjiao Yin; Feili Gong; Zhuoya Li (Cell and Tissue Research, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

A new highly oxygenated daphnane diterpene esters from the flower buds of Daphne genkwa - Hai-Long Jiang; Rui Wang; Jian-Yong Li; Yan-Ping Shi (Natural Product Research, 2015)

Regulation of three isoforms of SOD gene by environmental stresses in citrus red mite, Panonychus citri - Ying-Cai Feng; Chong-Yu Liao; Wen-Kai Xia; Xuan-Zhao Jiang; Feng Shang; Guo-Rui Yuan; Jin-Jun Wang (Experimental and Applied Acarology, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Heterogeneity of Bacterial Community Compositions in Surface Sediments of Three Lake Zones in Lake Taihu - Rui Huang; Dayong Zhao; Cuiling Jiang; Meng Wang (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Spatial-temporal patterns of major ion chemistry and its controlling factors in the Manasarovar Basin, Tibet - Zhijun Yao; Rui Wang; Zhaofei Liu; Shanshan Wu; Liguang Jiang (Journal of Geographical Sciences, 2015)

Isolation of a new lycodine alkaloid from Lycopodium japonicum - Jichun Wu; Huanqin Wang; Yanfang Ma; Jinhe Jiang; Rui Zhan; Yegao Chen (Natural Product Research, 2015)

Estimation of soil erosion in some sections of Lower Jinsha River based on RUSLE - Liguang Jiang; Zhijun Yao; Zhaofei Liu; Shanshan Wu; Rui Wang; Lei Wang (Natural Hazards, 2015)

Factors controlling the long-term temporal and spatial patterns of nitrate-nitrogen export in a dairy farming watershed - Rui Jiang; Chun-ying Wang; Ryusuke Hatano; Kanta Kuramochi; Atsushi Hayakawa; Krishna P. Woli (Environmental Monitoring and Assessment, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

Chemical modification, characterization and bioactivity of a released exopolysaccharide (r-EPS1) from Lactobacillus plantarum 70810 - Kun Wang; Wei Li; Xin Rui; Teng Li; Xiaohong Chen; Mei Jiang; Mingsheng Dong (Glycoconjugate Journal, 2015)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

A new algorithm for fine acquisition of GPS carrier frequency - Kedong Wang; Rui Jiang; Yong Li; Ning Zhang (GPS Solutions, 2014)

Protective Effects of Selenium on Mercury Induced Immunotoxic Effects in Mice by Way of Concurrent Drinking Water Exposure - Xuan Li; Daqiang Yin; Jiang Li; Rui Wang (Archives of Environmental Contamination and Toxicology, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

The apoptosis of peripheral blood lymphocytes promoted by hyperbaric oxygen treatment contributes to attenuate the severity of early stage acute pancreatitis in rats - Xuewei Bai; Zengfu Song; Yanmei Zhou; Shangha Pan; Feng Wang; Zuoming Guo; Maitao Jiang; Gang Wang; Rui Kong; Bei Sun (Apoptosis, 2014)

Cellular boron allocation and pectin composition in two citrus rootstock seedlings differing in boron-deficiency response - Gui-Dong Liu; Rui-Dong Wang; Lei-Chao Liu; Li-Shu Wu; Cun-Cang Jiang (Plant and Soil, 2013)

Genome-wide Analysis of the Distribution of AP2/ERF Transcription Factors Reveals Duplication and Elucidates their Potential Function in Chinese Cabbage (Brassica rapa ssp. pekinensis) - Meng-Yao Li; Feng Wang; Qian Jiang; Rui Li; Jing Ma; Ai-Sheng Xiong (Plant Molecular Biology Reporter, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

A novel Trichoderma species isolated from soil in Guizhou, T. guizhouense - Qi-Rui Li; Ping Tan; Yu-Lan Jiang; Kevin D. Hyde; Eric H. C. Mckenzie; Ali H. Bahkali; Ji-Chuan Kang; Yong Wang (Mycological Progress, 2013)

Boron distribution and mobility in navel orange grafted on citrange and trifoliate orange - Gui-Dong Liu; Rui-Dong Wang; Li-Shu Wu; Shu-Ang Peng; Yun-Hua Wang; Cun-Cang Jiang (Plant and Soil, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Effects of flue gas desulfurization gypsum by-products on microbial biomass and community structure in alkaline–saline soils - Ming Li; Lili Jiang; Zhaojun Sun; Jinzhi Wang; Yichao Rui; Lei Zhong; Yanfen Wang; Paul Kardol (Journal of Soils and Sediments, 2012)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

Calculations of rock matrix modulus based on a linear regression relation - Xi-Lei He; Zhen-Hua He; Rui-Liang Wang; Xu-Ben Wang; Lian Jiang (Applied Geophysics, 2011)

Identification of a Novel Bacterial K+ Channel - Guanghua Tang; Bo Jiang; Yuan Huang; Ming Fu; Lingyun Wu; Rui Wang (The Journal of Membrane Biology, 2011)

Time-dependent oxidative stress and histopathological changes in Cyprinus carpio L. exposed to microcystin-LR - Jinlin Jiang; Xueyuan Gu; Rui Song; Qian Zhang; Jinju Geng; Xiaorong Wang; Liuyan Yang (Ecotoxicology, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Synthesis, Crystal Structure, Interaction with BSA and Antibacterial Activity of La(III) and Sm(III) Complexes with Enrofloxacin - Yan-Jun Wang; Rui-Ding Hu; Dong-Hua Jiang; Ping-Hua Zhang; Qiu-Yue Lin; Yun-Yun Wang (Journal of Fluorescence, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

Activation of NF-κB by nucleocapsid protein of the porcine reproductive and respiratory syndrome virus - Rui Luo; Liurong Fang; Yunbo Jiang; Hui Jin; Yanwei Wang; Dang Wang; Huanchun Chen; Shaobo Xiao (Virus Genes, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Genome-wide identification and evaluation of novel internal control genes for Q-PCR based transcript normalization in wheat - Xiang-Yu Long; Ji-Rui Wang; Thérèse Ouellet; Hélène Rocheleau; Yu-Ming Wei; Zhi-En Pu; Qian-Tao Jiang; Xiu-Jing Lan; You-Liang Zheng (Plant Molecular Biology, 2010)

Identification, localization, and characterization of putative USP genes in barley - Wei-Tao Li; Yu-Ming Wei; Ji-Rui Wang; Chun-Ji Liu; Xiu-Jin Lan; Qian-Tao Jiang; Zhi-En Pu; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

Molecular diversity and phylogenetic analyses of y-type high-molecular-weight glutenin promoters from different genomes in Triticeae - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Plant Systematics and Evolution, 2010)

Molecular characterization of a member of a new species of grapevine viroid - Dongmei Jiang; Rui Guo; Zujian Wu; Hongqing Wang; Shifang Li (Archives of Virology, 2009)

Identity of an ABA-activated 46 kDa mitogen-activated protein kinase from Zea mays leaves: partial purification, identification and characterization - Haidong Ding; Aying Zhang; Jinxiang Wang; Rui Lu; Hong Zhang; Jianhua Zhang; Mingyi Jiang (Planta, 2009)

Molecular characterization of grapevine yellow speckle viroid-2 (GYSVd-2) - Dongmei Jiang; Zhixiang Zhang; Zujian Wu; Rui Guo; Hongqing Wang; Peige Fan; Shifang Li (Virus Genes, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Cloning, expression, and pharmacological activity of BmK AS, an active peptide from scorpion Buthus martensii Karsch - Jian-Hua Shao; Yue-Qiu Wang; Xiao-Yan Wu; Rui Jiang; Rong Zhang; Chun-Fu Wu; Jing-Hai Zhang (Biotechnology Letters, 2007)

Involvement of PDCD5 in the regulation of apoptosis in fibroblast-like synoviocytes of rheumatoid arthritis - Ning Wang; Hou-Shan Lu; Zhen-Peng Guan; Tie-Zheng Sun; Ying-Yu Chen; Guo-Rui Ruan; Zhan-Kun Chen; Jun Jiang; Chu-Jie Bai (Apoptosis, 2007)

A high-molecular-weight glutenin subunit gene 1Dx2.1 from Xinjiang rice wheat - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Cereal Research Communications, 2005)

Polymorphism of the mouse gene for the interleukin 10 receptor alpha chain (Il10ra) and its association with the autoimmune phenotype - Zan-Mei Qi; Jun Wang; Zheng-Rong Sun; Feng-Mao Ma; Qing-Rui Zhang; Sachiko Hirose; Yi Jiang (Immunogenetics, 2005)

Detection of known mutations in hypertrophic cardiomyopathy using oligonucleotide microarrays assisted by improved base stacking hybridization - Dong Wang; Yan Li; Rui Zhang; Di Jiang; Xuemei Ma; Yuxiang Zhou; Jing Cheng (Biotechnology Letters, 2003)

Endogenous KV channels in human embryonic kidney (HEK-293) cells - Bo Jiang; Xianfeng Sun; Kun Cao; Rui Wang (Molecular and Cellular Biochemistry, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)